Toner, toner storage unit and image forming apparatus

JP7643202B2Active Publication Date: 2025-03-11RICOH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021102643
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-21
Publication Date
2025-03-11
Estimated Expiration
2041-06-21

AI Technical Summary

Benefits of technology

【0007】 本発明の一態様は、優れた、低温定着性、耐熱保存性、画像光沢性及びクリーニング性を有するトナーを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643202000003
    Figure 0007643202000003
  • Figure 0007643202000004
    Figure 0007643202000004
  • Figure 0007643202000005
    Figure 0007643202000005
Patent Text Reader

Abstract

To provide a toner having excellent low temperature fixability, heat-resistant storage property, image glossiness, and cleaning property.SOLUTION: An aspect of a toner according to the present invention is a toner containing a toner base particle including a crystalline polyester resin and an amorphous resin. The toner base particle includes a plurality of organic fine particles arranged on its surface while partially embedded in the surface. The standard deviation of the inter-particle distance between the adjacent organic fine particles not in contact with each other is 600 nm or less. When the radius of the cross section of the toner is R, the area of the crystalline polyester resin in an area inside a true circle with a radius of R / 2 is less than 20% of the total area of the crystalline polyester resin in the cross section. The ratio of the crystalline polyester resin occupying the surface of the toner base particle is less than 15%.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a toner, a toner storage unit, and an image forming apparatus. [Background technology]

[0002] Image forming devices using toner, such as multi-function peripherals (MFPs) and printers, are widely used in various places, including offices. Toner is required to have low-temperature fixing property and heat-resistant storage property in order to reduce power consumption during fixing to save energy, and to improve resistance to high temperatures and high humidity during storage and transportation.

[0003] As a toner having low-temperature fixing property, for example, a toner for developing electrostatic images containing toner base particles containing a binder resin containing a crystalline polyester resin and an amorphous resin, and a release agent has been proposed (for example, see Patent Document 1). In this toner for developing electrostatic images, the area of ​​the region having a lamellar crystal structure was 1 to 20% of the surface area of ​​the toner base particles when the surface of the toner base particles dyed with ruthenium was observed with a scanning electron microscope. In addition, when the cross section of the toner base particles dyed with ruthenium was observed with a transmission electron microscope, the area was 4 to 16% of the cross-sectional area of ​​the toner base particles. Summary of the Invention [Problem to be solved by the invention]

[0004] However, the toner described in Patent Document 1 is insufficient to achieve both low-temperature fixability and heat-resistant storage stability, which are required at a high level in recent years. In addition, although the toner described in Patent Document 1 has been examined for gloss variation of an image at a specific fixing temperature, gloss variation due to fixing temperature has not been examined, and there is a possibility that sufficient image gloss cannot be obtained depending on the fixing temperature. Furthermore, the toner described in Patent Document 1 may not be able to completely remove toner attached to the photoconductor, and may not be able to obtain sufficient cleaning properties.

[0005] An object of one aspect of the present invention is to provide a toner having excellent low-temperature fixing property, heat-resistant storage stability, image gloss and cleaning property. [Means for solving the problem]

[0006] One embodiment of the toner according to the present invention is a toner containing toner base particles including a crystalline polyester resin and an amorphous polyester resin, the toner base particles including a plurality of organic fine particles arranged in a state where at least a part of the organic fine particles are embedded in the surface of the toner base particles, the organic fine particles have a volume average particle diameter of 10 nm to 40 nm, and the content of the organic fine particles in the toner is 0.2% by mass to 5% by mass; The standard deviation of the distance between adjacent particles of the organic fine particles that are not in contact with each other is 81nm~590nm When the radius of the cross section of the toner is R, the area of ​​the crystalline polyester resin in the inner region of a perfect circle having a radius of R / 2 is 1 / 2 of the total area of ​​the crystalline polyester resin in the cross section. More than 5% The proportion of the surface area of ​​the toner base particle occupied by the crystalline polyester resin is less than 15%. Effect of the Invention

[0007] An embodiment of the present invention can provide a toner having excellent low-temperature fixing property, heat-resistant storage stability, image glossiness and cleaning property. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a first schematic diagram of a cross section of a toner according to an embodiment. [Diagram 2] 3 is a TEM photograph showing an example of a cross section of a toner according to an embodiment. [Diagram 3] FIG. 2 is a second schematic diagram of a cross section of the toner according to an embodiment. [Figure 4] FIG. 4 is a third schematic diagram of a cross section of a toner according to an embodiment. [Diagram 5] FIG. 1 is a schematic diagram illustrating an example of an image forming apparatus according to an embodiment. [Figure 6] FIG. 2 is a schematic diagram illustrating an example of a process cartridge according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described in detail. Note that the embodiments are not limited by the following description, and can be appropriately modified without departing from the gist of the present invention. In addition, in this specification, "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower and upper limits, unless otherwise specified.

[0010] <Toner> The toner according to an embodiment contains toner base particles including a crystalline polyester resin and an amorphous (non-crystalline) polyester resin as a binder resin, and may contain a plurality of organic fine particles arranged in a state where at least a part of the particles is embedded in the surface of the toner base particles.

[0011] [Ratio of area of ​​crystalline polyester resin in deep region to total area in cross section of toner] When the radius of the cross section of the toner is R, the area of ​​the crystalline polyester resin in the region A (deep region) inside the perfect circle with a radius of R / 2 shown in FIG. 1 is less than 20% of the total area of ​​the crystalline polyester resin in the cross section, more preferably less than 18%, and even more preferably less than 15%. The area of ​​the crystalline polyester resin may be 5% or more of the total area of ​​the crystalline polyester resin in the cross section. The crystalline polyester rapidly reduces in viscosity due to melting during fixing of the toner according to one embodiment, and is fixed by being compatible with the amorphous polyester resin. Due to such properties, the toner according to one embodiment exhibits good low-temperature fixing properties. When the area of ​​the crystalline polyester resin in the deep region is 20% or more of the total area of ​​the crystalline polyester resin in the cross section, the variation in glossiness due to the fixing temperature increases, and the image glossiness of the image after fixing decreases. By making the area of ​​the crystalline polyester resin in the deep region less than 20% of the total area of ​​the crystalline polyester resin in the cross section, the variation in glossiness due to the fixing temperature is reduced, and excellent image glossiness is obtained.

[0012] The ratio of the area of ​​the crystalline polyester resin in the deep region to the total area of ​​the cross section of the toner can be calculated by dyeing the toner according to one embodiment with ruthenium, observing the cross section of the toner with a transmission electron microscope (TEM), and analyzing the obtained image. Specifically, this can be done by the following method.

[0013] The toner is embedded in an epoxy resin and sliced ​​to a thickness of 100 nm using a microtome. The cross section of the toner is then observed by TEM to confirm the structure in which the crystalline polyester resin is in contact with the release agent. A 0.5% aqueous solution of ruthenium tetroxide may be used for dyeing. The crystalline polyester resin can be determined from the contrast and shape of the toner cross section in the TEM image. For example, a TEM photograph showing an example of a cross section of a toner according to an embodiment is shown in FIG. 2. As shown in FIG. 2, linear or lamellar crystals (see the broken line in FIG. 2) scattered in the non-crystalline polyester resin in the toner can be determined to be crystalline polyester resin. The cross sections of about 50 toners may be adjusted so that one slice contains them. From the obtained TEM photograph, the total area of ​​the crystalline polyester resin in the toner cross section and the area of ​​the crystalline polyester resin in the deep region are measured, and the ratio of the area of ​​the crystalline polyester resin in the deep region to the total area of ​​the toner cross section can be calculated.

[0014] In addition, when the cross-sectional shape of the toner is an ellipse or a distorted circle, the radius R of the cross-section of the toner is the major axis R of the cross-section of the toner, as shown in FIG. max and minor axis R min The average value of (R max +R min ) / 2, and the area A inside a perfect circle with a radius of R / 2 can be considered as the deep area.

[0015] [Proportion of the surface of the toner base particle occupied by crystalline polyester resin] The ratio of the crystalline polyester resin occupying the surface of the toner base particle (surface 0) is less than 15%, and more preferably 10% or less. The crystalline polyester rapidly reduces its viscosity by melting during fixing of the toner according to an embodiment, and is compatible with the amorphous polyester resin and fixed. Due to such properties, the toner according to an embodiment exhibits good low-temperature fixability. If the ratio of the crystalline polyester resin occupying the surface of the toner base particle is less than 4%, the fixability of the toner deteriorates. If the ratio of the crystalline polyester resin occupying the surface of the toner base particle exceeds 15%, the heat-resistant storage stability of the toner deteriorates. By setting the ratio of the crystalline polyester resin occupying the surface of the toner base particle within the above range, it is possible to achieve both good low-temperature fixability and heat-resistant storage stability.

[0016] The ratio of the crystalline polyester resin to the surface of the toner base particle can be calculated by observing the cross section of the toner with a TEM in the same manner as described above and analyzing the obtained image. Specifically, the length of the crystalline polyester resin present on the circumference of the toner cross section and the circumference of the toner cross section are measured from the obtained TEM image, and the ratio of the length of the crystalline polyester resin present on the circumference of the toner cross section to the circumference of the toner cross section, that is, the ratio of the crystalline polyester resin to the surface of the toner base particle can be calculated.

[0017] [Volume average particle size of organic fine particles and standard deviation of the distance between non-contacting organic fine particles] At least a part of the organic fine particles is embedded in the surface of the toner base particle. The volume average particle diameter of the organic fine particles is 10 nm to 40 nm. By reducing the particle diameter of the particles present on the surface of the toner base particle, good cleaning properties can be maintained without impairing low-temperature fixability.

[0018] In addition, the standard deviation of the distance between adjacent organic fine particles that are not in contact with each other is 600 nm or less, preferably 300 nm or less, and more preferably 200 nm or less. By uniformly arranging the organic fine particles on the surface of the toner base body with gaps, the exposure of materials such as crystalline polyester can be suppressed without impeding heat transfer to the toner base particles during fixing of the toner, and the heat-resistant storage stability of the toner can be improved. In addition, the adhesion strength of inorganic fine particles such as silica and titanium can be appropriately adjusted when they are externally added to the surface of the toner base particles. As a result, it has been found that a certain amount of inorganic fine particles are liberated from the toner base body during cleaning, and the liberated inorganic fine particles are deposited on the contact surface between the cleaning blade and the photoconductor, thereby obtaining good cleaning properties. In addition, the amount of liberated inorganic fine particles can be appropriately controlled, thereby suppressing the occurrence of filming.

[0019] The standard deviation of the distance between organic fine particles that are not in contact with each other can be calculated by observing the toner according to one embodiment with a scanning electron microscope (SEM) and analyzing the obtained image. Specifically, the standard deviation can be calculated by the following method.

[0020] (1) The external additives are removed as much as possible by ultrasonic wave to release the additives, and the toner is made into a state close to the toner base particles. The obtained toner is observed by SEM. (2) External additives and fillers containing Si are detected by observing the backscattered electron image. (3) The image obtained in (2) is binarized using image processing software (ImageJ) to remove external additives and fillers. (4) Next, a secondary electron image was observed at the same position as in (2). Organic fine particles are not observed in the reflected electron image, but only in the secondary electron image. Therefore, by comparing with the image obtained in (3), the fine particles present in the areas other than the remaining external additives and filler (areas other than those excluded in (3)) are determined to be organic fine particles. Using image processing software, the distance between the fine particles (the center-to-center distance of the fine particles) is measured. The standard deviation of the distance between organic fine particles can be calculated using the following formula (I), where the distance between the fine particles is x.

[0021]

number

[0022] [Crystalline polyester resin and amorphous polyester resin] The toner according to an embodiment includes a polyester resin having a crystalline polyester resin and an amorphous polyester resin as a binder resin. The toner according to an embodiment may contain a binder resin other than the polyester resin. The toner according to an embodiment may contain other components such as a colorant and a release agent, if necessary, in addition to the binder resin.

[0023] (Crystalline polyester resin) Crystalline polyester resins have high crystallinity and therefore exhibit a thermal melting characteristic that causes a sudden drop in viscosity near the fixing start temperature. By using a crystalline polyester resin having such characteristics together with an amorphous polyester resin, the heat-resistant storage stability is good due to the crystallinity until just before the melting start temperature, and at the melting start temperature, a sudden drop in viscosity (sharp melt) occurs due to the melting of the crystalline polyester resin, which is then compatible with the amorphous polyester resin, and both are fixed by a sudden drop in viscosity, resulting in a toner that has both good heat-resistant storage stability and low-temperature fixing ability. In addition, the release width (the difference between the minimum fixing temperature and the high-temperature offset occurrence temperature) also shows good results.

[0024] The crystalline polyester resin is obtained by using a polyhydric alcohol and a polycarboxylic acid such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, or a derivative thereof. In this embodiment, the crystalline polyester resin refers to a resin obtained by using a polyhydric alcohol and a polycarboxylic acid such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, or a derivative thereof, as described above, and does not belong to the crystalline polyester resin, for example, a prepolymer and a resin obtained by reacting the prepolymer with at least one of a crosslinking reaction and an elongation reaction. In addition, the prepolymer refers to a reaction product of the polyester of the modified polyester contained in the amorphous polyester resin and a polyisocyanate, that is, a reaction precursor that reacts with a curing agent, as described later.

[0025] The presence or absence of crystallinity of the crystalline polyester resin can be confirmed by a crystal analysis X-ray diffraction device (for example, X'Pert Pro MRD Philips). The measurement method is described below.

[0026] First, the target sample is ground in a mortar to prepare a powdered sample, and the powdered sample is evenly applied to a sample holder.Then, the sample holder is set in the diffraction device, and measurements are performed to obtain a diffraction spectrum.

[0027] When the peak half-width of the peak with the highest peak intensity among the peaks obtained in the range of 20°<2θ<25° among the obtained diffraction peaks is 2.0 or less, it is judged to have crystallinity. In contrast to crystalline polyester resins, polyester resins that do not show the above-mentioned state are called amorphous polyester resins in this embodiment.

[0028] The conditions for the X-ray diffraction measurements are as follows. [Measurement conditions] Tension kV: 45kV Current: 40mA MPSS Upper Gonio Scan mode:continuous Start angle: 3° End angle: 35° Angle Step: 0.02° Lucident beam optics Divergence slit: Div slit 1 / 2 Diffraction beam optics Anti scatter slit:As fixed 1 / 2 Receiving slit:Prog rec slit

[0029] -Polyhydric alcohol- The polyhydric alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyhydric alcohol include diols and trihydric or higher alcohols.

[0030] Examples of the diol include saturated aliphatic diols. Examples of the saturated aliphatic diol include linear saturated aliphatic diols and branched saturated aliphatic diols. Among these, linear saturated aliphatic diols are preferred, and linear saturated aliphatic diols having 2 to 12 carbon atoms are more preferred. If the saturated aliphatic diol is a branched type, the crystallinity of the crystalline polyester resin may decrease, resulting in a decrease in melting point. In addition, if the carbon number of the saturated aliphatic diol exceeds 12, it becomes difficult to obtain a practical material. It is more preferred that the carbon number is 12 or less.

[0031] Examples of the saturated aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-eicosanediol, etc. Among these, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred in terms of high crystallinity of the crystalline polyester resin and excellent sharp melt properties.

[0032] Examples of trihydric or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, etc. These may be used alone or in combination of two or more.

[0033] -Polycarboxylic acids- The polyvalent carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include divalent carboxylic acids and trivalent or higher carboxylic acids.

[0034] Examples of the divalent carboxylic acid include saturated aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; and aromatic dicarboxylic acids such as dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid; and further, anhydrides of these acids and lower (carbon number: 1 to 3) alkyl esters of these acids.

[0035] Examples of trivalent or higher carboxylic acids include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, and the like, as well as anhydrides and lower (carbon number 1 to 3) alkyl esters thereof.

[0036] The polycarboxylic acid may contain a dicarboxylic acid having a sulfonic acid group in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. Furthermore, the polycarboxylic acid may contain a dicarboxylic acid having a double bond in addition to the saturated aliphatic dicarboxylic acid or aromatic dicarboxylic acid. These may be used alone or in combination of two or more.

[0037] The crystalline polyester resin is preferably composed of a linear saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a linear saturated aliphatic diol having 2 to 12 carbon atoms. That is, the crystalline polyester resin preferably has a constitutional unit derived from a saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a constitutional unit derived from a saturated aliphatic diol having 2 to 12 carbon atoms. This is preferable in that the resin has high crystallinity and excellent sharp melting properties, and can therefore exhibit excellent low-temperature fixability.

[0038] The melting point of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 60° C. to 80° C. If the melting point is 60° C. to 80° C., melting of the crystalline polyester resin is suppressed, the heat-resistant storage stability of the toner can be maintained, and the crystalline polyester resin can be sufficiently melted by heating during fixing, so that low-temperature fixability can be maintained.

[0039] The melting point of the crystalline polyester resin can be determined from a DSC curve obtained by differential scanning calorimetry (DSC). For example, from the DSC curves obtained by DSC measurement, the DSC curve at the first temperature rise can be selected using the analysis program in the Q-200 system, and the endothermic peak top temperature at the first temperature rise of the target sample can be determined as the melting point. Similarly, the DSC curve at the second temperature rise can be selected, and the endothermic peak top temperature at the second temperature rise of the target sample can be determined as the melting point.

[0040] The molecular weight of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint that a low molecular weight with a sharp molecular weight distribution is excellent in low temperature fixability, and a large amount of low molecular weight components reduces heat resistant storage stability, it is preferable that the orthodichlorobenzene soluble portion of the crystalline polyester resin has a weight average molecular weight Mw of 3000 to 30000, a number average molecular weight Mn of 1000 to 10000, and Mw / Mn of 1.0 to 10, as measured by gel permeation chromatography (GPC).More preferably, the weight average molecular weight Mw is 5000 to 15000, the number average molecular weight Mn is 2000 to 10000, and Mw / Mn is 1.0 to 5.0.

[0041] The acid value of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint of affinity between paper and resin, in order to achieve the desired low-temperature fixability, it is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, while in order to improve high-temperature offset resistance, it is preferably 45 mgKOH / g or less.

[0042] The hydroxyl value of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose. In order to achieve the desired low-temperature fixability and good charging characteristics, the hydroxyl value is preferably 0 mgKOH / g to 50 mgKOH / g, and more preferably 5 mgKOH / g to 50 mgKOH / g.

[0043] The molecular structure of the crystalline polyester resin can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 Or 990±10cm -1 One method is to detect a crystalline polyester resin that has absorption based on the δCH (out-of-plane bending vibration) of olefin.

[0044] The content of the crystalline polyester resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 3 to 20 parts by mass, more preferably 5 to 15 parts by mass, relative to 100 parts by mass of the toner. If the content is less than 3 parts by mass, the sharp melting by the crystalline polyester resin is insufficient, so that the low-temperature fixing property may be poor, and if it exceeds 20 parts by mass, the heat-resistant storage stability may be reduced and the image may be easily fogged. If the content is within the more preferred range, it is advantageous in that both high image quality and low-temperature fixing property are excellent.

[0045] (Amorphous polyester resin) The amorphous polyester resin is preferably a linear polyester resin. The amorphous polyester resin is preferably an unmodified polyester resin. The unmodified polyester resin is a polyester resin obtained by using a polyhydric alcohol and a polycarboxylic acid such as a polycarboxylic acid, a polycarboxylic acid anhydride, or a polycarboxylic acid ester or a derivative thereof, and is not modified by an isocyanate compound or the like.

[0046] The amorphous polyester preferably contains a diol component and a dicarboxylic acid component as constituents, and preferably contains 40 mol % or more of alkylene glycol. The polyester resin component may or may not contain a crosslinking component as a constituent.

[0047] Examples of the diol component include alkylene (carbon number 2-3) oxide (average number of added moles 1-10) adducts of bisphenol A such as polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane and polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane; ethylene glycol, propylene glycol; hydrogenated bisphenol A; and alkylene (carbon number 2-3) oxide (average number of added moles 1-10) adducts of hydrogenated bisphenol A. These may be used alone or in combination of two or more.

[0048] Examples of the dicarboxylic acid component include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, and succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms, such as dodecenylsuccinic acid and octylsuccinic acid. It is particularly preferable to contain 50 mol % or more of terephthalic acid. These may be used alone or in combination of two or more.

[0049] The amorphous polyester resin may contain at least one of a trivalent or higher carboxylic acid and a trivalent or higher alcohol at the end of the resin chain in order to adjust the acid value and the hydroxyl value.

[0050] Examples of trivalent or higher carboxylic acids include trimellitic acid, pyromellitic acid, and acid anhydrides thereof.

[0051] The trihydric or higher alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include trihydric or higher aliphatic alcohols, trihydric or higher polyphenols, and alkylene oxide adducts of trihydric or higher polyphenols.

[0052] Examples of trihydric or higher aliphatic alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and sorbitol.

[0053] Examples of trivalent or higher polyphenols include trisphenol PA, phenol novolac, and cresol novolac.

[0054] Examples of the alkylene oxide adducts of trivalent or higher polyphenols include those obtained by adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to trivalent or higher polyphenols.

[0055] The amorphous polyester resin component preferably contains a crosslinking component. As the crosslinking component, it is preferable to contain a trivalent or higher aliphatic alcohol, and from the viewpoint of the gloss and image density of the fixed image, it is more preferable to contain a trivalent or tetravalent aliphatic alcohol. As the trivalent or tetravalent aliphatic alcohol, it is preferable to use a trivalent or tetravalent aliphatic polyhydric alcohol component having 3 to 10 carbon atoms. The crosslinking component may be only a trivalent or higher aliphatic alcohol.

[0056] The trihydric or higher aliphatic alcohol can be appropriately selected depending on the purpose, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, dipentaerythritol, etc. These trihydric or higher aliphatic alcohols may be used alone or in combination of two or more kinds.

[0057] As the crosslinking component of the amorphous polyester resin component, a trivalent or higher carboxylic acid or an epoxy compound, etc. can be used. However, from the viewpoint of preventing unevenness and obtaining sufficient gloss and image density, it is more preferable to contain a trivalent or higher aliphatic alcohol as the crosslinking component.

[0058] The molecular weight of the amorphous polyester resin component is not particularly limited and can be appropriately selected according to the purpose. However, if the molecular weight is too low, the heat-resistant storage stability of the toner and durability against stress such as stirring in a developing machine may decrease. If the molecular weight is too high, the viscoelasticity of the toner when melted may increase, and low-temperature fixability may decrease. In addition, if the amount of the component having a molecular weight of 600 or less is too large, the heat-resistant storage stability of the toner and durability against stress such as stirring in a developing machine may decrease, and if the amount of the component having a molecular weight of 600 or less is too small, the low-temperature fixability may decrease.

[0059] Therefore, in the GPC measurement, the weight average molecular weight Mw is preferably 3000 to 10000, and the number average molecular weight Mn is preferably 1000 to 4000. Moreover, Mw / Mn is preferably 1.0 to 4.0. Moreover, the weight average molecular weight Mw is more preferably 4000 to 7000, the number average molecular weight Mn is more preferably 1500 to 3000, and Mw / Mn is more preferably 1.0 to 3.5.

[0060] The THF-soluble component having a molecular weight of 600 or less is preferably 2% by mass to 10% by mass, and the polyester resin may be extracted with methanol to remove the component having a molecular weight of 600 or less for purification.

[0061] The acid value of the amorphous polyester resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 1 mgKOH / g to 50 mgKOH / g, more preferably 5 mgKOH / g to 30 mgKOH / g. If the acid value is 1 mgKOH / g or more, the toner tends to be negatively charged, and furthermore, the affinity between the paper and the toner is improved when the toner is fixed to the paper, and low-temperature fixability can be improved. On the other hand, if the acid value is more than 50 mgKOH / g, the charging stability, especially the charging stability against environmental changes, may decrease.

[0062] The hydroxyl value of the amorphous polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 5 mgKOH / g or more.

[0063] The glass transition temperature Tg of the amorphous polyester resin is preferably 40° C. to 65° C., more preferably 45° C. to 65° C., and even more preferably 50° C. to 60° C. When the glass transition temperature Tg is 40° C. or higher, the toner has improved heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has improved filming resistance. On the other hand, when the glass transition temperature Tg is 65° C. or lower, the toner is less susceptible to deformation due to heat and pressure during fixing, and low-temperature fixing ability is improved.

[0064] The content of the amorphous polyester resin component is preferably 80 parts by mass to 90 parts by mass with respect to 100 parts by mass of the toner.

[0065] [Polyester resin insoluble in tetrahydrofuran (modified polyester)] The toner base particles may contain a polyester resin (hereinafter, modified polyester) that imparts plasticity to the toner base particles. The polyester resin insoluble in tetrahydrofuran (THF) in the toner base particles lowers the glass transition temperature Tg and melt viscosity, and ensures low-temperature fixability, while having a branched structure in the molecular skeleton and a three-dimensional network structure of molecular chains. Therefore, the toner base particles can have rubber-like properties in that they deform but do not flow at low temperatures.

[0066] The modified polyester has a structure represented by any one of the following structural formulas (1) to (3), in which R2, which is a polyester or modified polyester moiety, and R1, which corresponds to a branched structure, are bonded via a urethane or urea group. (1)R1-(NHCONH-R2)n- (2)R1-(NHCOO-R2)n- (3) R1-(OCONH-R2)n- (In the above formula, n=3, R1 represents an isocyanurate skeleton, and R2 represents a group derived from any one of a polyester resin containing a polycarboxylic acid and a polyol, and a modified polyester resin obtained by modifying a polyester with an isocyanate.)

[0067] Since the modified polyester has at least one of a urethane bond and a urea bond in the branched structure portion, the urethane bond or the urea bond behaves like a pseudo-crosslinking point, and the rubber-like properties of the modified polyester are strengthened, making it possible to produce a toner with excellent heat resistance storage stability and high-temperature offset resistance.

[0068] The modified polyester is not particularly limited as long as it is formed by bonding R2 corresponding to a polyester or modified polyester and R1 corresponding to a branched structural portion via a urethane or urea group, and can be appropriately selected depending on the purpose.

[0069] Methods for bonding R1 and R2 include, but are not limited to, the following methods.

[0070] (a) A method in which a diol component and a dicarboxylic acid component are subjected to an esterification reaction to produce a polyester polyol (R2) having hydroxyl groups at the terminals, and the resulting polyester polyol is reacted with an isocyanurate (R1). (b) A method in which a diol component and a dicarboxylic acid component are subjected to an ester reaction to produce a polyester polyol (R2) having hydroxyl groups at the terminals, the resulting polyester polyol is reacted with a divalent polyisocyanate to produce an isocyanate-modified polyester (R2), and the resulting isocyanate-modified polyester is reacted with an isocyanurate (R1) in the presence of pure water.

[0071] -Diol component- The diol component is not particularly limited and can be appropriately selected depending on the purpose. For example, aliphatic diols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol; diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and the like. Examples of the diol include diols having an oxyalkylene group such as polypropylene glycol and polytetramethylene glycol; alicyclic diols such as 1,4-cyclohexanedimethanol and hydrogenated bisphenol A; alicyclic diols to which alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide have been added; bisphenols such as bisphenol A, bisphenol F, and bisphenol S; and alkylene oxide adducts of bisphenols, such as bisphenols to which alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide have been added. These diols may be used alone or in combination of two or more.

[0072] -Dicarboxylic acid component- The dicarboxylic acid component is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include aliphatic dicarboxylic acids, aromatic dicarboxylic acids, etc. In addition, anhydrides, lower (1 to 3 carbon atoms) alkyl esters, or halides of these may be used.

[0073] The aliphatic dicarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aliphatic dicarboxylic acid include succinic acid, adipic acid, sebacic acid, dodecanedioic acid, maleic acid, and fumaric acid.

[0074] The aromatic dicarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose, but aromatic dicarboxylic acids having 8 to 20 carbon atoms are preferred.

[0075] The aromatic dicarboxylic acid having 8 to 20 carbon atoms is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include phthalic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, etc. Among these, aromatic dicarboxylic acids having 8 to 12 carbon atoms are preferred. These dicarboxylic acids may be used alone or in combination of two or more.

[0076] -Polyisocyanate- The polyisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyisocyanate include diisocyanates and tri- or higher valent isocyanates.

[0077] Examples of diisocyanates include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, isocyanurates, and those blocked with phenol derivatives, oximes, caprolactams, etc.

[0078] The aliphatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aliphatic diisocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, methyl 2,6-diisocyanatocaproate, octamethylene diisocyanate, decamethylene diisocyanate, dodecamethylene diisocyanate, tetradecamethylene diisocyanate, trimethylhexane diisocyanate, and tetramethylhexane diisocyanate.

[0079] The alicyclic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alicyclic diisocyanate include isophorone diisocyanate and cyclohexylmethane diisocyanate.

[0080] The aromatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aromatic diisocyanate include tolylene diisocyanate, diisocyanatodiphenylmethane, 1,5-naphthylene diisocyanate, 4,4'-diisocyanatodiphenyl, 4,4'-diisocyanato-3,3'-dimethyldiphenyl, 4,4'-diisocyanato-3-methyldiphenylmethane, and 4,4'-diisocyanato-diphenyl ether.

[0081] The aromatic aliphatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. For example, α,α,α',α'-tetramethylxylylene diisocyanate is exemplified.

[0082] The isocyanurates are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include tris(isocyanatoalkyl)isocyanurate, tris(isocyanatocycloalkyl)isocyanurate, etc. These polyisocyanates may be used alone or in combination of two or more kinds.

[0083] Examples of the trivalent or higher isocyanate include lysine triisocyanate, or a product obtained by reacting a trivalent or higher alcohol with a diisocyanate, or a product obtained by reacting a polyisocyanate to form an isocyanurate, etc. Among these, it is more preferable to use a polyisocyanate having an isocyanurate skeleton, since it acts as a stronger crosslinking point and is more excellent in heat resistance storage stability and high-temperature offset resistance.

[0084] The trivalent isocyanate is preferably 0.2 mol% to 1.0 mol% based on the resin components in the THF insoluble matter of the toner. When a crosslinked structure is formed by a trivalent isocyanate, the molecular chain has a high cohesive force due to pseudo-crosslinking by urethane or urea bonds at the crosslinking points, so that the heat-resistant storage stability can be improved even with a low crosslinking density, and low-temperature fixability can be achieved at a high level. When the trivalent isocyanate component is less than 0.2 mol%, the formation of a branched structure becomes insufficient, and the network structure becomes non-uniform at the starting point, which may deteriorate the heat-resistant storage stability and filming resistance. When the trivalent isocyanate component is more than 1.0 mol%, a dense crosslinked structure is formed, which may deteriorate the low-temperature fixability.

[0085] It is also possible to further react the hydroxyl groups remaining in the polyol obtained by either of the above (a) or (b) with a divalent or higher polyisocyanate to form a prepolymer, which can then be reacted with a curing agent in the toner production process.

[0086] - Hardener - The curing agent is not particularly limited as long as it is a curing agent that can react with a prepolymer (the reaction product of the polyester R2 in the structural formulas (1) to (3) of the modified polyester and polyisocyanate, i.e., a reaction precursor to be reacted with a curing agent) to produce a polyester resin, and can be appropriately selected according to the purpose. Examples of the curing agent include active hydrogen group-containing compounds.

[0087] The active hydrogen group in the active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include hydroxyl groups (alcoholic hydroxyl groups and phenolic hydroxyl groups), amino groups, carboxyl groups, mercapto groups, etc. These may be used alone or in combination of two or more.

[0088] The active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose, but amines are preferred because they are capable of forming a urea bond.

[0089] The amines are not particularly limited and can be appropriately selected according to the purpose, and examples thereof include diamines, trivalent or higher amines, amino alcohols, amino mercaptans, amino acids, and blocked amino groups thereof. These may be used alone or in combination of two or more. Among these, diamines and mixtures of diamines and small amounts of trivalent or higher amines are preferred.

[0090] The diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include aromatic diamines, alicyclic diamines, and aliphatic diamines. The aromatic diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include phenylenediamine, diethyltoluenediamine, and 4,4'-diaminodiphenylmethane. The alicyclic diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include 4,4'-diamino-3,3'-dimethyldicyclohexylmethane, diaminocyclohexane, and isophoronediamine. The aliphatic diamine is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include ethylenediamine, tetramethylenediamine, and hexamethylenediamine.

[0091] The trivalent or higher amine is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include diethylenetriamine and triethylenetetramine.

[0092] The amino alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino alcohol include ethanolamine and hydroxyethylaniline.

[0093] The amino mercaptan is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino mercaptan include aminoethyl mercaptan and aminopropyl mercaptan.

[0094] The amino acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino acid include aminopropionic acid and aminocaproic acid.

[0095] The blocked amino group is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include ketimine compounds and oxazoline compounds obtained by blocking the amino group with ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0096] During the toner production process, at least one of a urethane bond and a urea bond is generated by reaction with a curing agent, and the resulting resin behaves like a strong crosslinking point, thereby enhancing the rubber-like properties of the modified polyester and providing further excellent heat resistance storage stability and high-temperature offset resistance. Therefore, it is more preferable that the R2 portion is a modified polyester resin modified with an isocyanate.

[0097] In order to lower the glass transition temperature Tg of the modified polyester and to easily impart the property of deformation at low temperatures, the modified polyester contains a diol component as a constituent component, and the diol component preferably contains an aliphatic diol having 3 to 12 carbon atoms, and more preferably contains an aliphatic diol having 4 to 12 carbon atoms.

[0098] The modified polyester preferably contains 50 mol % or more, more preferably 80 mol % or more, and even more preferably 90 mol % or more of an aliphatic diol having 3 to 12 carbon atoms.

[0099] Examples of the aliphatic diol having 3 to 12 carbon atoms include 1,3-propanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol.

[0100] In particular, in the modified polyester, it is more preferable that the diol component is an aliphatic diol having 4 to 12 carbon atoms, the main chain of the diol component has an odd carbon number, and the diol component has an alkyl group in the side chain.

[0101] Examples of the aliphatic diol having 4 to 12 carbon atoms and an odd-numbered main chain and an alkyl group on the side chain include aliphatic diols represented by the following general formula (1). HO-(CR1R2)n-OH (1) (In formula (1), R1 and R2 each independently represent a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. n represents an odd number from 3 to 9. In the n repeating units, R1 may be the same or different. In the n repeating units, R2 may be the same or different.)

[0102] In order to lower the glass transition temperature Tg of the modified polyester and easily impart the property of deformation at low temperatures, the amorphous polyester resin preferably contains 50 mol % or more of an aliphatic diol having 3 to 12 carbon atoms in the total alcohol components.

[0103] In order to lower the glass transition temperature Tg of the modified polyester and to easily impart the property of deformation at low temperatures, the amorphous polyester resin preferably contains a dicarboxylic acid component as a constituent component, and the dicarboxylic acid component preferably contains an aliphatic dicarboxylic acid having 4 to 12 carbon atoms.

[0104] The polyester resin preferably contains 30 mol % or more of an aliphatic dicarboxylic acid having 4 to 12 carbon atoms.

[0105] Examples of the aliphatic dicarboxylic acid having 4 to 12 carbon atoms include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid.

[0106] The glass transition temperature Tg of the modified polyester is preferably from -60°C to 0°C, more preferably from -40°C to -20°C. If the glass transition temperature Tg is less than -60°C, the flow of the toner at low temperatures cannot be suppressed, and the heat-resistant storage stability and filming resistance may deteriorate. If the glass transition temperature is more than 0°C, the toner cannot be sufficiently deformed by heating and pressure during fixing, and low-temperature fixing properties may be insufficient.

[0107] The glass transition temperature Tg of the toner according to one embodiment at the first temperature rise in DSC 1st The glass transition temperature Tg 1st The glass transition temperature Tg of the THF-soluble component of the toner in the second heating period of the DSC is -45°C to 5°C. 2nd It is preferable that the temperature is 20°C to 65°C.

[0108] Glass transition temperature Tg 1st and Tg 2nd can be obtained from the DSC curve obtained in the DSC measurement. For example, the DSC curve at the first temperature rise is selected from the DSC curves obtained in the DSC measurement using the analysis program in the Q-200 system, and the glass transition temperature Tg 1st Similarly, the DSC curve during the second heating is selected, and the glass transition temperature Tg 2nd can be sought.

[0109] The weight average molecular weight of the modified polyester is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 20,000 to 1,000,000 as measured by GPC.

[0110] The weight average molecular weight of the modified polyester refers to the molecular weight of the reaction product obtained by reacting a reactive precursor with a curing agent.

[0111] If the weight average molecular weight is less than 20,000, the toner tends to flow at low temperatures, and the heat-resistant storage stability may be poor.

[0112] Furthermore, the viscosity at the time of melting is decreased, and the high-temperature offset resistance may be deteriorated.

[0113] The content of the modified polyester is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 to 15 parts by mass, and more preferably 5 to 10 parts by mass, in 100 parts by mass of the toner.

[0114] [Amorphous hybrid resin] The toner base particles preferably contain an amorphous hybrid resin in the toner base particles. The amorphous hybrid resin preferably contains one or more composite resins containing a condensation polymerization resin and a styrene resin, and two polymerization resin components each having an independent reaction path are partially chemically bonded, and at least one of the two polymerization resin components preferably contains the same polymerization resin component as the polyester resin. The reaction path means the type of polymerization reaction (condensation polymerization, vinyl polymerization, etc.). In addition, having independent reaction paths means a state in which, under certain conditions, while a part is polymerized, there is no functional group that reacts with the other. Specifically, the above-mentioned amorphous hybrid resin refers to an amorphous hybrid resin obtained by independently synthesizing, for example, a polyester block (condensation polymerization resin) by condensation polymerization and a styrene acrylic block (styrene resin) by vinyl polymerization. In addition, when the reaction paths are not independent from each other, for example, the amorphous hybrid resin refers to an amorphous hybrid resin obtained by reacting a polyester block with a styrene acrylic block.

[0115] The above-mentioned constitution can improve the dispersibility of the crystalline polyester resin in the toner base particles. In addition, by controlling the exposure of the crystalline polyester to the surface of the toner base particles and dispersing the crystalline polyester uniformly inside the toner base particles, it is possible to contribute to achieving both low-temperature fixability and heat-resistant storage stability.

[0116] The toner base particles preferably contain a resin obtained by mixing, as one of the raw material monomers, a monomer that can react with both of the raw material monomers of the two polymerizable resins (a bireactive monomer) in addition to the mixture of raw material monomers of the two polymerizable resins, each of which has an independent reaction pathway.

[0117] The bireactive monomer is preferably a monomer having at least one functional group selected from the group consisting of a hydroxyl group, a carboxyl group, an epoxy group, a primary amino group, and a secondary amino group, and an ethylenically unsaturated bond in the molecule, and by using such a bireactive monomer, the dispersibility of the resin that becomes the dispersed phase can be improved.Specific examples of the bireactive monomer include acrylic acid, fumaric acid, methacrylic acid, citraconic acid, maleic acid, etc., and among these, acrylic acid, methacrylic acid, and fumaric acid are preferred.

[0118] The amount of the bireactive monomer used is preferably 0.1 to 10 parts by mass with respect to 100 parts by mass of the raw material monomer of the condensation polymerization resin. In this embodiment, the bireactive monomer is treated as a monomer different from the raw material monomer of the condensation polymerization resin and the raw material monomer of the addition polymerization resin due to its unique performance.

[0119] In the present embodiment, when the amorphous hybrid resin is obtained by carrying out two polymerization reactions using the above-mentioned raw material monomer mixture and bireactive monomer, the polymerization reactions do not need to proceed and be completed simultaneously in time. The reaction temperature and time are appropriately selected according to the respective reaction mechanisms, and the reactions may proceed and be completed.

[0120] For example, the following method is preferred for producing an amorphous hybrid resin. First, raw material monomers for a condensation polymerization resin, raw material monomers for an addition polymerization resin, a bireactive monomer, a catalyst such as a polymerization initiator, and the like are mixed. Then, an addition polymerization resin component having a functional group capable of undergoing a condensation polymerization reaction is obtained by a radical polymerization reaction mainly at 50°C to 180°C. Next, after increasing the reaction temperature to 190°C to 270°C, a condensation polymerization resin component is formed mainly by a condensation polymerization reaction.

[0121] The softening point of the amorphous hybrid resin is 80°C to 170°C, preferably 90°C to 160°C, and more preferably 95°C to 155°C.

[0122] The weight ratio of the crystalline polyester resin to the amorphous hybrid resin is not particularly limited, but the ratio of polyester resin:amorphous hybrid resin is preferably 50 / 100 to 200 / 100.

[0123] As the raw material monomer for the condensation polymerization resin, it is preferable to use a succinic acid derivative as the carboxylic acid component.

[0124] The raw material monomers for styrene-based resins are styrene, α-methylstyrene, vinyltoluene, and other styrene derivatives.

[0125] The content of the styrene derivative in the raw material monomer of the styrene-based resin is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.

[0126] Examples of raw material monomers for styrene-based resins that can be used other than styrene derivatives include (meth)acrylic acid alkyl esters; ethylenically unsaturated monoolefins such as ethylene and propylene; diolefins such as butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; esters of ethylenically monocarboxylic acids such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as vinyl methyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone.

[0127] Among these, (meth)acrylic acid alkyl esters are preferred from the viewpoints of low-temperature fixability and charge stability of the toner. From the above viewpoints, the number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester is preferably 1 to 22, more preferably 8 to 18. The number of carbon atoms in the alkyl ester refers to the number of carbon atoms derived from the alcohol component constituting the ester. Specific examples include methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, (iso or tertiary)butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, and (iso)stearyl (meth)acrylate.

[0128] From the viewpoints of low-temperature fixing property, storage stability and charging stability of the toner, the content of the (meth)acrylic acid alkyl ester is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less, of the raw material monomers of the styrene-based resin.

[0129] The content of the amorphous hybrid resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 15% by mass or more relative to the number of parts of the crystalline polyester. If the content is less than 15%, the effect of dispersing the crystalline polyester inside is weak, and there is a possibility that the crystalline polyester is excessively arranged on the surface.

[0130] [Organic fine particles] The organic fine particles may be contained in a state where at least a part of them is embedded in the surface of the toner base particle. The organic fine particles may be arranged in a scattered state on the surface of the toner base particle, not in a state where they are layered covering the surface of the toner base particle.

[0131] The organic fine particles are preferably one or more kinds of styrene-acrylic resins having at least a carboxylic acid, and are obtained by homopolymerizing or copolymerizing a vinyl monomer.

[0132] The organic fine particles are preferably composed of two types of styrene acrylic resins (a1) and (a2), and more preferably have a core-shell structure with the styrene acrylic resin (a1) as the shell and the styrene acrylic resin (a2) as the core.

[0133] (Resin (a1)) The resin (a1) is a polymer obtained by homopolymerizing or copolymerizing a vinyl monomer. Examples of the vinyl monomer include the following (1) to (10).

[0134] (1) Vinyl hydrocarbons Examples of the vinyl hydrocarbon include (1-1) aliphatic vinyl hydrocarbons, (1-2) alicyclic vinyl hydrocarbons, and (1-3) aromatic vinyl hydrocarbons.

[0135] (1-1) Aliphatic vinyl hydrocarbons Aliphatic vinyl hydrocarbons include alkenes and alkadienes. Specific examples of alkenes include ethylene, propylene, and α-olefins. Specific examples of alkadienes include butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene, and 1,7-octadiene.

[0136] (1-2) Alicyclic vinyl hydrocarbons Alicyclic vinyl hydrocarbons include mono- or di-cycloalkenes and alkadienes, and specific examples include (di)cyclopentadiene, terpene, and the like.

[0137] (1-3) Aromatic vinyl hydrocarbons Examples of aromatic vinyl hydrocarbons include styrene and its hydrocarbyl (alkyl, cycloalkyl, aralkyl and / or alkenyl) substituted derivatives, and specific examples thereof include α-methylstyrene, 2,4-dimethylstyrene and vinylnaphthalene.

[0138] (2) Carboxyl-containing vinyl monomers and their salts Examples of the carboxyl group-containing vinyl monomer and its salt include unsaturated monocarboxylic acids (salts) having 3 to 30 carbon atoms, unsaturated dicarboxylic acids (salts), and their anhydrides (salts), and their monoalkyl (carbon number 1 to 24) esters or salts.

[0139] Specific examples thereof include carboxyl group-containing vinyl monomers such as (meth)acrylic acid, (anhydride) maleic acid, maleic acid monoalkyl esters, fumaric acid, fumaric acid monoalkyl esters, crotonic acid, itaconic acid, itaconic acid monoalkyl esters, itaconic acid glycol monoether, citraconic acid, citraconic acid monoalkyl esters, and cinnamic acid, and metal salts thereof.

[0140] In the present embodiment, the term "(salt)" refers to an acid or a salt thereof. For example, an unsaturated monocarboxylic acid (salt) having 3 to 30 carbon atoms refers to an unsaturated monocarboxylic acid or a salt thereof.

[0141] "(Meth)acrylic" means methacrylic acid or acrylic acid. That is, "(meth)acryloyl" means methacryloyl or acryloyl, and "(meth)acrylate" means methacrylate or acrylate.

[0142] (3) Sulfonic acid-containing vinyl monomers, vinyl sulfate monoesters, and their salts Examples of the sulfonic acid group-containing vinyl monomer, vinyl sulfate monoester, and salts thereof include alkene sulfonic acids (salts) having 2 to 14 carbon atoms, alkyl sulfonic acids (salts) having 2 to 24 carbon atoms, sulfo(hydroxy)alkyl-(meth)acrylates (salts) or (meth)acrylamides (salts), and alkylaryl sulfosuccinic acids (salts). Specifically, examples of the alkene sulfonic acids having 2 to 14 carbon atoms include vinyl sulfonic acid (salts), examples of the alkyl sulfonic acids having 2 to 24 carbon atoms include α-methylstyrene sulfonic acid (salts), and examples of the sulfo(hydroxy)alkyl-(meth)acrylates (salts) or (meth)acrylamides (salts) include sulfopropyl(meth)acrylates (salts), sulfate esters (salts), or sulfonic acid group-containing vinyl monomers (salts).

[0143] (4) Phosphate-containing vinyl monomers and their salts: Examples of the phosphoric acid group-containing vinyl monomer and its salt include (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphoric acid monoester (salt) and (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphonic acid (salt).

[0144] Specific examples of the (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphate monoester (salt) include 2-hydroxyethyl (meth)acryloyl phosphate (salt) and phenyl-2-acryloyloxyethyl phosphate (salt).

[0145] Specific examples of (meth)acryloyloxyalkyl (carbon number: 1 to 24)phosphonic acids (salts) include 2-acryloyloxyethylphosphonic acid (salts).

[0146] Examples of the salts of (2) to (4) above include alkali metal salts (sodium salts, potassium salts, etc.), alkaline earth metal salts (calcium salts, magnesium salts, etc.), ammonium salts, amine salts, and quaternary ammonium salts.

[0147] (5) Hydroxyl-containing vinyl monomers Examples of hydroxyl group-containing vinyl monomers include hydroxystyrene, N-methylol (meth)acrylamide, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, (meth)allyl alcohol, crotyl alcohol, isocrotyl alcohol, 1-buten-3-ol, 2-buten-1-ol, 2-butene-1,4-diol, propargyl alcohol, 2-hydroxyethyl propenyl ether, and sucrose allyl ether.

[0148] (6) Nitrogen-containing vinyl monomers Examples of the nitrogen-containing vinyl monomer include an amino group-containing vinyl monomer, an amide group-containing vinyl monomer, a nitrile group-containing vinyl monomer, a quaternary ammonium cation group-containing vinyl monomer, and a nitro group-containing vinyl monomer.

[0149] Examples of the amino group-containing vinyl monomer include aminoethyl (meth)acrylate.

[0150] Examples of the amide group-containing vinyl monomer include (meth)acrylamide and N-methyl(meth)acrylamide.

[0151] Examples of the nitrile group-containing vinyl monomer include (meth)acrylonitrile, cyanostyrene, and cyanoacrylate.

[0152] Examples of the vinyl monomer containing a quaternary ammonium cation group include quaternized products of tertiary amine group-containing vinyl monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and diallylamine (which are quaternized using a quaternizing agent such as methyl chloride, dimethyl sulfate, benzyl chloride, or dimethyl carbonate).

[0153] Nitro group-containing vinyl monomers include nitrostyrene.

[0154] (7) Epoxy group-containing vinyl monomer Examples of the epoxy group-containing vinyl monomer include glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and p-vinylphenyl phenyl oxide.

[0155] (8) Halogen-containing vinyl monomers Examples of halogen-containing vinyl monomers include vinyl chloride, vinyl bromide, vinylidene chloride, allyl chloride, chlorostyrene, bromostyrene, dichlorostyrene, chloromethylstyrene, tetrafluorostyrene, and chloroprene.

[0156] (9) Vinyl esters, vinyl (thio)ethers, vinyl ketones (9-1) Vinyl ester Examples of vinyl esters include vinyl acetate, vinyl butyrate, vinyl propionate, vinyl butyrate, diallyl phthalate, diallyl adipate, isopropenyl acetate, vinyl methacrylate, methyl 4-vinyl benzoate, cyclohexyl methacrylate, benzyl methacrylate, phenyl (meth)acrylate, vinyl methoxyacetate, vinyl benzoate, ethyl α-ethoxyacrylate, alkyl (meth)acrylates having an alkyl group having 1 to 50 carbon atoms [methyl (meth)acrylate], ) acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, behenyl (meth)acrylate, etc.)], dialkyl fumarate (wherein the two alkyl groups are linear, branched or alicyclic groups having 2 to 8 carbon atoms), dialkyl Examples of the polyalkylene glycol include maleates (wherein the two alkyl groups are straight-chain, branched-chain or alicyclic groups having 2 to 8 carbon atoms), poly(meth)allyloxyalkanes (diallyloxyethane, triallyloxyethane, tetraallyloxyethane, tetraallyloxypropane, tetraallyloxybutane, tetramethallyloxyethane, etc.), vinyl monomers having polyalkylene glycol chains (polyethylene glycol (molecular weight 300) mono(meth)acrylate, polypropylene glycol (molecular weight 500) monoacrylate, methyl alcohol ethylene oxide 10 mol adduct (meth)acrylate, lauryl alcohol ethylene oxide 30 mol adduct (meth)acrylate, etc.), poly(meth)acrylates (poly(meth)acrylates of polyhydric alcohols: ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyethylene glycol di(meth)acrylate, etc.).

[0157] (9-2) Vinyl(thio)ether An example of the vinyl (thio)ether is vinyl methyl ether.

[0158] (9-3) Vinyl ketone An example of the vinyl ketone is vinyl methyl ketone.

[0159] (10) Other vinyl monomers Other vinyl monomers include tetrafluoroethylene, fluoroacrylate, isocyanatoethyl (meth)acrylate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate.

[0160] For the resin (a1), the above vinyl monomers (1) to (10) may be used alone or in combination of two or more.

[0161] From the viewpoint of low-temperature fixability of organic fine particles, the resin (a1) preferably contains a styrene-(meth)acrylic acid ester copolymer and a (meth)acrylic acid ester copolymer, and more preferably contains a styrene-(meth)acrylic acid ester copolymer.

[0162] (resin (a2)) The resin (a2) may be a polymer obtained by homopolymerizing a vinyl monomer having a carboxyl group or copolymerizing it with another monomer. The vinyl monomer may be the same polymer as that used for the resin (a1).

[0163] Resin (a2) is a resin containing methacrylic acid and / or acrylic acid in a total amount of preferably 10% by mass to 60% by mass, more preferably 30% by mass to 50% by mass, based on the total mass of resin (a2).

[0164] As for the resin (a2), like the resin (a1), from the viewpoint of low-temperature fixing property of organic fine particles, a styrene-(meth)acrylic acid ester copolymer and a (meth)acrylic acid ester copolymer are preferable, and a styrene-(meth)acrylic acid ester copolymer is more preferable.

[0165] The viscoelastic loss modulus G'' of the resin (a1) at 100° C. and a frequency of 1 Hz is from 1.5 to 100 Mpa, preferably from 1.7 to 30 Mpa, and more preferably from 2.0 to 10 Mpa.

[0166] The loss modulus G'' of the viscoelastic properties of resin (a2) at a frequency of 1 Hz and at 100°C is 0.01 to 1.0 Mpa, preferably 0.02 to 0.5 Mpa, and more preferably 0.05 to 0.3 Mpa. Within this range, toner particles are easily formed in which organic fine particles containing resin (a1) and resin (a2) as components within the same particle are attached to the surface of the toner particle.

[0167] The loss modulus G″ of the viscoelastic properties is measured, for example, by using the following viscoelasticity measuring device. Equipment: ARES-24A (Rheometrics) Fixture: 25mm parallel plate Frequency: 1Hz Distortion rate: 10% Heating rate: 5℃ / min

[0168] The loss modulus G″ of the viscoelastic properties of resins (a1) and (a2) at a frequency of 1 Hz and 100° C. can be adjusted by changing the types and composition ratio of the constituent monomers or by adjusting the polymerization conditions (types and amounts of initiator and chain transfer agent, reaction temperature, etc.).

[0169] Specifically, for example, by using the following composition, it is possible to adjust each G'' to be within the above-mentioned range.

[0170] (1) Regarding the glass transition temperature Tg1 calculated from the constituent monomers of the resin (a1) and the glass transition temperature Tg2 calculated from the constituent monomers of the resin (a2), the glass transition temperature Tg1 is preferably 0 to 150° C., and more preferably 50 to 100° C. The glass transition temperature Tg2 is preferably −30 to 100° C., and more preferably 0 to 80° C., and more preferably 30 to 60° C.

[0171] The glass transition temperature Tg calculated from the constituent monomers is a value that can be calculated by the Fox method.

[0172] Here, the Fox method [TGFox, Phys. Rev., 86, 652 (1952)] is a method for estimating the Tg of a copolymer from the Tg of each homopolymer represented by the following formula. 1 / Tg=W1 / Tg1+W2 / Tg2++Wn / Tgn (In the formula, Tg is the glass transition temperature (expressed in absolute temperature) of the copolymer, Tg1, Tg2...Tgn are the glass transition temperatures (expressed in absolute temperature) of the homopolymers of each monomer component, and W1, W2...Wn are the weight fractions of each monomer component.)

[0173] (2) Regarding the calculated acid value (AV1) of the resin (a1) and the calculated acid value (AV2) of the resin (a2), the calculated acid value (AV1) is preferably 75 mgKOH / g to 400 mgKOH / g, and more preferably 150 mgKOH / g to 300 mgKOH / g.

[0174] The calculated acid value (AV2) is set to 0 mgKOH / g to 50 mgKOH / g, more preferably 0 mgKOH / g to 20 mgKOH / g, and most preferably 0 mgKOH / g.

[0175] The calculated acid value is a theoretical acid value calculated from the molar amount of acidic groups contained in the constituent monomers and the total weight of the constituent monomers.

[0176] As a constituent monomer satisfying the conditions (1) and (2), for the resin (a1), for example, there can be mentioned a resin containing, as a constituent monomer, preferably 10% by mass to 80% by mass, and more preferably 30% by mass to 60% by mass of styrene, and a total of preferably 10% by mass to 60% by mass, and more preferably 30% by mass to 50% by mass of at least one of methacrylic acid and acrylic acid, based on the total mass of the resin (a1).

[0177] Moreover, the resin (a2) may, for example, contain, as a constituent monomer, preferably 10% by mass to 100% by mass, and more preferably 30% by mass to 90% by mass of styrene, based on the total mass of the resin (a2), and contain, in total, preferably 0% by mass to 7.5% by mass, and more preferably 0% by mass to 2.5% by mass of at least one of methacrylic acid and acrylic acid, based on the total mass of the resin (a2).

[0178] (3) By adjusting the polymerization conditions (type and amount of initiator and chain transfer agent, reaction temperature, etc.), the number average molecular weights Mn1 and Mn2 of resin (a1) and resin (a2) are preferably set to 2,000 to 2,000,000, and more preferably 20,000 to 200,000, and the number average molecular weight Mn2 is preferably set to 1,000 to 1,000,000, and more preferably 10,000 to 100,000.

[0179] The acid value (AVa1) of the resin (a1) is preferably 75 mgKOH / g to 400 mgKOH / g, more preferably 150 mgKOH / g to 300 mgKOH / g. Within this range, the resin fine particles containing vinyl units, which contain the resin (a1) and the resin (a2) as constituents in the same particle, tend to form particles attached to the surface of the toner base particle.

[0180] Resin (a1) having an acid value within this range is a resin that contains methacrylic acid and / or acrylic acid in a total amount of preferably 10 to 60 mass %, more preferably 30 to 50 mass %, based on the total mass of resin (a1).

[0181] From the viewpoint of low-temperature fixability, the resin (a2) has an acid value AVa2 of preferably 0 mgKOH / g to 50 mgKOH / g, more preferably 0 mgKOH / g to 20 mgKOH / g, and even more preferably 0 mgKOH / g.

[0182] Resin (a2) having an acid value within this range is a resin that contains methacrylic acid and / or acrylic acid in a total amount of preferably 0 to 7.5% by mass, and more preferably 0 to 2.5% by mass, based on the total mass of resin (a2).

[0183] The acid value in this embodiment is measured by the method of JIS K0070:1992.

[0184] The glass transition temperature Tg of the resin (a1) is preferably higher than the glass transition temperature Tg of the resin (a2). Within this range, the toner having the resin fine particles attached to the surface of the toner base particle can be easily formed, and the toner according to the embodiment has an excellent balance of low-temperature fixability.

[0185] The glass transition temperature Tg of the resin (a1) is more preferably 10° C. or more higher, and particularly preferably 20° C. or more higher, than the glass transition temperature Tg of the resin (a2).

[0186] The glass transition temperature Tg of the resin (a1) is preferably 0° C. to 150° C., and more preferably 50° C. to 100° C. When the glass transition temperature Tg of the resin (a1) is 0° C. or higher, the storage stability of the organic resin particles is excellent, and when it is 150° C. or lower, the low-temperature fixability of the organic resin particles is less hindered.

[0187] The glass transition temperature Tg of the resin (a2) is preferably −30° C. to 100° C., more preferably 0° C. to 80° C., and most preferably 30° C. to 60° C. When the glass transition temperature Tg of the resin (a2) is −30° C. or higher, the storage stability of the organic fine particles is excellent, and when it is 100° C. or lower, the low-temperature fixability of the organic fine particles is less hindered.

[0188] The glass transition temperature Tg is measured by the method (DSC) specified in ASTM D3418-82 using "DSC20, SSC / 580, manufactured by Seiko Instruments Inc."

[0189] The solubility parameter (hereinafter abbreviated as SP value) of the resin (a1) is preferably 9 (cal / cm) from the viewpoint of ease of forming a toner in which resin fine particles containing the resin (a1) and the resin (a2) as constituent components in the same particle are attached to the surface of the toner base particle. 3 ) 1 / 2 ~13(cal / cm 3 ) 1 / 2 and more preferably 9.5 (cal / cm 3 ) 1 / 2 ~12.5(cal / cm 3 ) 1 / 2 and more preferably 10.5 (cal / cm 3 ) 1 / 2 ~11.5(cal / cm 3 ) 1 / 2 It is.

[0190] The SP value of the resin (a1) can be adjusted by changing the types and composition ratio of the constituent monomers.

[0191] The SP value of the resin (a2) is preferably 8.5 (cal / cm) from the viewpoint of ease of forming a toner in which resin fine particles containing the resin (a1) and the resin (a2) as constituent components in the same particle are attached to the surface of the toner base particle. 3 ) 1 / 2 ~12.5(cal / cm 3 ) 1 / 2 and more preferably 9 (cal / cm 3 ) 1 / 2 ~12(cal / cm 3 ) 1 / 2 and more preferably 10 (cal / cm 3 ) 1 / 2 ~11(cal / cm 3 ) 1 / 2 It is.

[0192] The SP value of the resin (a2) can be adjusted by changing the types and composition ratio of the constituent monomers.

[0193] The SP value in this embodiment is calculated by the method by Fedors [Polym. Eng. Sci. 14(2)152, (1974)].

[0194] From the viewpoint of the glass transition temperature Tg of the resin (a1) and copolymerizability with other monomers, the resin (a1) contains, as a constituent monomer, preferably 10% by mass to 80% by mass, more preferably 30% by mass to 60% by mass, based on the total mass of the resin (a1).

[0195] From the viewpoint of the glass transition temperature Tg of the resin (a2) and copolymerizability with other vinyl monomers, the resin (a2) contains, as a constituent monomer, preferably 10% by mass to 100% by mass, more preferably 30% by mass to 90% by mass, based on the total mass of the resin (a2).

[0196] The number average molecular weight Mn of the resin (a1) is preferably 2000 to 2000000, and more preferably 20000 to 200000. When the number average molecular weight Mn is 2000 or more, the storage stability of the organic fine particles is excellent, and when the number average molecular weight Mn is 2000000 or less, the low temperature fixability of the organic fine particles according to this embodiment is less hindered.

[0197] The weight average molecular weight Mw of the resin (a1) is preferably larger than the weight average molecular weight Mw of the resin (a2). When the weight average molecular weight Mw of the resin (a1) is larger than the weight average molecular weight Mw of the resin (a2), a good balance is achieved between the ease of forming a toner in which organic fine particles are attached to the surface of the toner base particles and the low temperature fixability of the toner according to one embodiment.

[0198] The weight average molecular weight Mw of the resin (a1) is more preferably at least 1.5 times, and particularly preferably at least 2.0 times, larger than the weight average molecular weight Mw of the resin (a2).

[0199] The weight average molecular weight Mw of the resin (a1) is preferably 20,000 to 20,000,000, and more preferably 200,000 to 2,000,000. When the weight average molecular weight Mw of the resin (a1) is 20,000 or more, the storage stability of the organic fine particles is excellent. When the weight average molecular weight Mw of the resin (a1) is 20,000,000 or less, the low temperature fixability of the organic fine particles is less hindered.

[0200] The number average molecular weight Mn of the resin (a2) is preferably 1000 to 1000000, and more preferably 10000 to 100000. When the number average molecular weight Mn of the resin (a2) is 1000 or more, the storage stability of the organic fine particles is excellent. When the number average molecular weight Mn of the resin (a2) is 1000000 or less, the low temperature fixability of the organic fine particles is less hindered.

[0201] The weight average molecular weight Mw of the resin (a2) is preferably 10,000 to 10,000,000, and more preferably 100,000 to 1,000,000. When the weight average molecular weight Mw of the resin (a2) is 10,000 or more, the storage stability of the organic fine particles is excellent. When the weight average molecular weight Mw of the resin (a2) is 10,000,000 or less, the low temperature fixability of the organic fine particles is less hindered.

[0202] It is particularly preferred that the weight average molecular weight Mw of resin (a1) is 200,000 to 2,000,000, the weight average molecular weight Mw of resin (a2) is 100,000 to 500,000, and the "weight average molecular weight Mw of resin (a1)" > "the weight average molecular weight Mw of resin (a2)".

[0203] In the present embodiment, the number average molecular weight Mn and the weight average molecular weight Mw can be measured by gel permeation chromatography (GPC) under the following conditions. Equipment: "HLC-8120" [Tosoh Corporation] Column: 2 "TSK GEL GMH6" [Tosoh Corporation] ·Measurement temperature: 40℃ Sample solution: 0.25% by mass tetrahydrofuran solution (undissolved matter was removed by filtration using a glass filter) ·Solution injection volume: 100μl Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) (molecular weight: 500, 1050, 2800, 5970, 9100, 18100, 37900, 96400, 190000, 355000, 1090000, 2890000) [manufactured by Tosoh Corporation]

[0204] The weight ratio of resin (a1) to resin (a2) in the organic fine particles is preferably 5 / 95 to 95 / 5, more preferably 25 / 75 to 75 / 25, and even more preferably 40 / 60 to 60 / 40. When the weight ratio of resin (a1) to resin (a2) is 5 / 95 or more, the toner according to the embodiment has excellent heat-resistant storage stability. When the weight ratio of resin (a1) to resin (a2) is 95 / 5 or less, a toner in which organic fine particles are attached to the surface of the toner base particles is easily formed.

[0205] Although the organic fine particles can be used alone, organic fine particles (A) made of two types of styrene acrylic resins (resins (a1) and (a2)) and organic fine particles (B) made of one type of styrene acrylic resin can be used in combination. The organic fine particles (A) and (B) mixed in advance during emulsification are uniformly attached to the surface of the toner base particles, and the organic fine particles (B) attached to the surface of the toner base particles and all or a part of the resin (a1) in the organic fine particles (A) are removed in a washing step described later, so that the organic fine particles (A) can be uniformly attached with gaps.

[0206] Methods for producing organic fine particles (A) containing resin (a1) and resin (a2) as constituent components within the same particle include known production methods, such as the following production methods (I) to (V). (I) A method of seed polymerization of constituent monomers of resin (a2) using fine particles of resin (a1) in an aqueous dispersion as seeds. (II) A method of seed polymerization of constituent monomers of resin (a1) using fine particles of resin (a2) in an aqueous dispersion as seeds. (III) A method in which a mixture of the resin (a1) and the resin (a2) is emulsified in an aqueous medium to obtain an aqueous dispersion of resin fine particles. (IV) A method in which a mixture of the resin (a1) and the constituent monomers of the resin (a2) is emulsified in an aqueous medium, and then the constituent monomers of the resin (a2) are polymerized to obtain an aqueous dispersion of organic fine particles. (V) A method in which a mixture of resin (a2) and monomers constituting resin (a1) is emulsified in an aqueous medium, and then the monomers constituting resin (a1) are polymerized to obtain an aqueous dispersion of organic fine particles.

[0207] In addition, the fact that the organic microparticles (A) contain resin (a1) and resin (a2) as constituent components within the same particle can be confirmed by observing element mapping images of a cut surface of the organic microparticles (A) using a known surface elemental analysis device (TOF-SIMS, EDX-SEM, etc.) and by observing electron microscope images of a cut surface of the organic microparticles (A) stained with a stain corresponding to the functional groups contained in the resin (a1) and resin (a2).

[0208] The organic fine particles obtained by the above method may be obtained as a mixture containing organic fine particles (A) containing resin (a1) and resin (a2) as constituent components within the same particle, as well as organic fine particles (B) containing resin (a1) as the only constituent resin component and resin fine particles containing resin (a2) as the only constituent resin component. In the composite process described below, the mixture may be used as is, or only the organic fine particles (A) may be isolated and used.

[0209] Specific examples of (I) include the following methods. First, the constituent monomers of the resin (a1) are polymerized by dropwise polymerization to produce an aqueous dispersion of resin fine particles containing the resin (a1). Then, the constituent monomers of (a2) are seed-polymerized using the aqueous dispersion as a seed, or (a1) previously produced by solution polymerization or the like is emulsified and dispersed in water. Then, the constituent monomers of the resin (a2) are seed-polymerized using the emulsified dispersion as a seed.

[0210] Specific examples of (II) include the following methods. First, the constituent monomers of the resin (a2) are polymerized by dropwise polymerization to produce an aqueous dispersion of resin fine particles containing the resin (a2). Then, the constituent monomers of the resin (a1) are seed-polymerized using the aqueous dispersion as a seed, or the resin (a2) previously produced by solution polymerization or the like is emulsified and dispersed in water. Then, the constituent monomers of the resin (a1) are seed-polymerized using the emulsified dispersion as a seed.

[0211] A specific example of (III) is a method in which a solution or melt containing resin (a1) and resin (a2) previously produced by solution polymerization or the like is mixed, and then the mixture is emulsified and dispersed in an aqueous medium.

[0212] Specific examples of (IV) include the following methods. First, resin (a1) previously produced by solution polymerization or the like is mixed with constituent monomers of resin (a2), and the resulting mixture is emulsified and dispersed in an aqueous medium, and the constituent monomers of resin (a2) are polymerized in the emulsion dispersion to produce resin (a1). Then, the mixture is emulsified and dispersed in an aqueous medium, and the constituent monomers of resin (a2) are polymerized in the emulsion dispersion.

[0213] Specific examples of (V) include the following methods. First, resin (a2) previously produced by solution polymerization or the like is mixed with the constituent monomers of resin (a1), and the resulting mixture is emulsified and dispersed in an aqueous medium, and the constituent monomers of resin (a1) are polymerized in the emulsion dispersion to produce resin (a2). Then, the mixture is emulsified and dispersed in an aqueous medium, and the constituent monomers of resin (a1) are polymerized in the emulsion dispersion.

[0214] Any of the production methods (I) to (V) is suitable.

[0215] The organic fine particles (A) are preferably used as an aqueous dispersion, and the aqueous medium of the dispersion can be any liquid containing water as an essential component. In this embodiment, since the organic fine particles and further a surfactant are provided on the surface of the toner, the aqueous medium can be an aqueous solution containing a surfactant in water.

[0216] The particle diameter of the organic fine particles is preferably 10 nm to 100 nm. If the particle diameter is less than 10 nm, the coverage rate on the toner surface increases, and low-temperature fixing performance may decrease. If the particle diameter exceeds 100 nm, the voids on the toner surface become large, and the effect of heat-resistant storage performance decreases.

[0217] The particle size of the organic fine particles can be measured by using a laser Doppler particle size distribution measuring device, by adding a sample to be measured to the measuring device using a dropper or syringe, etc. The measurement conditions are as follows. (Measurement conditions) Equipment: nanotrac UPA-150EX (manufactured by Nikkiso Co., Ltd.) Distribution display: Volume Number of channels: 52 ·Measurement time: 30sec Particle refractive index: 1.81 ·Temperature: 25℃ ·Particle shape: spherical ·Viscosity (CP): High temperature viscosity 0.797 Low temperature viscosity 1.002 Solvent refractive index: 1.333 Solvent: Water

[0218] The content of the organic fine particles (A) in the toner is preferably 0.2% by mass to 5% by mass. If the content is less than 0.2% by mass, the heat-resistant storage effect is not sufficiently obtained. If the content is more than 5%, the low-temperature fixation is significantly hindered.

[0219] The content of the organic fine particles (A) in the toner can be measured by a pyrolysis gas chromatograph. The measurement method is as follows. (Measurement conditions) Gas chromatograph: 7890B (Agilent Technologies) Pyrolysis equipment: EGA / PY-3030D (manufactured by Frontier Labs) ·Pyrolysis condition temperature: 600℃ Interface temperature: 400℃ Detector temperature: 320℃ Oven temperature: 50℃(10min)-<10℃ / min>-150℃(0min)-<20℃ / min>-320℃(3.5min) Column: UA5-30M-1F (30m x 0.25mm i.d., 1.0μm film) Detector: FID

[0220] The organic fine particles (B) are obtained in the same manner as the organic fine particles (A) composed of one type of styrene-acrylic resin. The organic fine particles (B) are preferably used as an aqueous dispersion, like the organic fine particles (A), and the aqueous medium of the dispersion can be any liquid containing water as an essential component without any restrictions.

[0221] In this embodiment, since organic fine particles and a surfactant are provided on the surface of the toner, the aqueous medium may be an aqueous solution containing a surfactant (D) in water.

[0222] The surfactant (D) includes nonionic surfactants (D1), anionic surfactants (D2), cationic surfactants (D3), amphoteric surfactants (D4) and other emulsifying dispersants (D5).

[0223] Furthermore, as necessary, an appropriate amount of sodium acetate, sodium citrate, sodium bicarbonate, etc. can be used as a buffer. Also, an appropriate amount of a water-soluble cellulose compound and an alkali metal salt of polymethacrylic acid, etc. can be used as a protective colloid. These may be used alone or in combination of two or more.

[0224] Examples of the nonionic surfactant (D1) include AO addition type nonionic surfactants and polyhydric alcohol type nonionic surfactants.

[0225] Examples of AO-addition type nonionic surfactants include EO adducts of aliphatic alcohols having 10 to 20 carbon atoms, EO adducts of phenols, EO adducts of nonylphenols, EO adducts of alkylamines having 8 to 22 carbon atoms, and EO adducts of poly(oxypropylene) glycols.

[0226] Examples of polyhydric alcohol-type nonionic surfactants include fatty acid (carbon number 8 to 24) esters of polyhydric (tri- to octahydric or higher) alcohols (carbon number 2 to 30) (e.g., glycerin monostearate, glycerin monooleate, sorbitan monolaurate, sorbitan monooleate, etc.) and alkyl (carbon number 4 to 24) poly(degree of polymerization 1 to 10) glycosides.

[0227] Examples of the anionic surfactant (D2) include ether carboxylic acids or salts thereof having a hydrocarbon group having 8 to 24 carbon atoms, sulfate esters or ether sulfate esters and salts thereof having a hydrocarbon group having 8 to 24 carbon atoms, sulfonates having a hydrocarbon group having 8 to 24 carbon atoms, sulfosuccinates having one or two hydrocarbon groups having 8 to 24 carbon atoms, phosphate esters or ether phosphate esters and salts thereof having a hydrocarbon group having 8 to 24 carbon atoms, fatty acid salts having a hydrocarbon group having 8 to 24 carbon atoms, and acylated amino acid salts having a hydrocarbon group having 8 to 24 carbon atoms.

[0228] Specifically, examples of ether carboxylic acids or salts thereof having a hydrocarbon group having 8 to 24 carbon atoms include sodium lauryl ether acetate and (poly)oxyethylene (number of moles added: 1 to 100) sodium lauryl ether acetate.

[0229] Examples of sulfates or ether sulfates having a hydrocarbon group having 8 to 24 carbon atoms and salts thereof include sodium lauryl sulfate, (poly)oxyethylene (number of moles added: 1 to 100) sodium lauryl sulfate, (poly)oxyethylene (number of moles added: 1 to 100) triethanolamine lauryl sulfate, and (poly)oxyethylene (number of moles added: 1 to 100) sodium coconut oil fatty acid monoethanolamide sulfate.

[0230] Examples of sulfonates having a hydrocarbon group having 8 to 24 carbon atoms include sodium dodecylbenzenesulfonate.

[0231] Examples of the phosphate ester or ether phosphate ester having a hydrocarbon group having 8 to 24 carbon atoms and salts thereof include sodium lauryl phosphate and sodium (poly)oxyethylene (addition mole number 1 to 100) lauryl ether phosphate.

[0232] Examples of the fatty acid salt having a hydrocarbon group having 8 to 24 carbon atoms include sodium laurate and triethanolamine laurate.

[0233] Examples of the acylated amino acid salts having a hydrocarbon group having 8 to 24 carbon atoms include sodium methyl coconut taurate, sodium coconut sarcosine, triethanolamine coconut sarcosine, N-triethanolamine coconut acyl-L-glutamate, sodium N-sodium coconut acyl-L-glutamate, and sodium lauroylmethyl-β-alanine.

[0234] The cationic surfactant (D3) may be of the quaternary ammonium salt type or amine salt type. Specifically, the quaternary ammonium salt type may be stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, and ethyl lanolin fatty acid aminopropyl ethyl dimethyl ammonium sulfate. The amine salt type may be stearic acid diethylaminoethylamide lactate, dilaurylamine hydrochloride, and oleylamine lactate.

[0235] Examples of the amphoteric surfactant (D4) include betaine-type amphoteric surfactants and amino acid-type amphoteric surfactants.

[0236] Examples of the betaine type amphoteric surfactant include coconut oil fatty acid amidopropyl dimethylaminoacetic acid betaine, lauryl dimethylaminoacetic acid betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl hydroxysulfobetaine.

[0237] Examples of the amino acid type amphoteric surfactant include sodium β-laurylaminopropionate.

[0238] Other emulsifying dispersants (D5) include, for example, reactive activators [which are not particularly limited as long as they have radical reactivity, and specifically include ADEKA REASOAP {registered trademark, manufactured by ADEKA Corporation} SE-10N, SR-10, SR-20, SR-30, ER-20, ER-30, AQUALON {registered trademark, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.} HS-10, KH-05, KH-10, KH-1025, ELEMINOL {registered trademark, manufactured by Sanyo Chemical Industries, Ltd.} JS-20, LATEMUL {registered trademark, manufactured by Kao Corporation} PD-104, PD-420, PD-4 No. 30, IONET (registered trademark, MO-200, manufactured by Sanyo Chemical Industries, Ltd.), polyvinyl alcohol, starch and derivatives thereof, cellulose derivatives such as carboxymethyl cellulose, methyl cellulose, and hydroxyethyl cellulose, carboxyl group-containing (co)polymers such as poly(sodium acrylate), and emulsifying dispersants having urethane groups or ester groups described in U.S. Pat. No. 5,906,704 (for example, polycaprolactone polyol and polyether diol linked with polyisocyanate).

[0239] As the surfactant (D), from the viewpoint of stabilizing the oil droplets during emulsification and dispersion, obtaining a desired shape, and sharpening the particle size distribution, preferred are nonionic surfactants (D1), anionic surfactants (D2), other emulsifying dispersants (D5), and combinations thereof. More preferred are combinations of nonionic surfactants (D1) and other emulsifying dispersants (D5), and combinations of anionic surfactants (D2) and other emulsifying dispersants (D5).

[0240] In addition to the resin (a1) and the resin (a2), the organic fine particles (A) in this embodiment may contain other resin components, an initiator (and its residue), a chain transfer agent, an antioxidant, a plasticizer, a preservative, a reducing agent, an organic solvent, and the like.

[0241] Examples of other resin components include vinyl resins other than the resins used in resin (a1) and resin (a2), polyurethane resins, epoxy resins, polyester resins, polyamide resins, polyimide resins, silicon resins, phenol resins, melamine resins, urea resins, aniline resins, ionomer resins, and polycarbonate resins.

[0242] Examples of the initiator (and its residue) include known radical polymerization initiators, etc. Specific examples include persulfate initiators such as potassium persulfate and ammonium persulfate, azo initiators such as azobisisobutyronitrile, organic peroxides such as benzoyl peroxide, cumene hydroperoxide, tertiary butyl hydroperoxide, tertiary butyl peroxyisopropyl monocarbonate and tertiary butyl peroxybenzoate, and hydrogen peroxide.

[0243] Examples of the chain transfer agent include n-dodecyl mercaptan, tert-dodecyl mercaptan, n-butyl mercaptan, 2-ethylhexyl thioglycolate, 2-mercaptoethanol, β-mercaptopropionic acid, and α-methylstyrene dimer.

[0244] Examples of the antioxidant include phenol compounds, paraphenylenediamine, hydroquinone, organic sulfur compounds, and organic phosphorus compounds.

[0245] The phenolic compounds include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,2'-methylene-bis-(4-methyl-6-t-butylphenol), 2,2'-methylene-bis-(4-ethyl-6-t-butylphenol), 4,4'-thiobis-(3-methyl-6-t-butylphenol), 4,4'-butylidenebis-(3-methyl -6-t-butylphenol), 1,1,3-tris-(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, and tocopherol.

[0246] Examples of paraphenylenediamines include N-phenyl-N'-isopropyl-p-phenylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, N-phenyl-N-sec-butyl-p-phenylenediamine, N,N'-di-isopropyl-p-phenylenediamine, and N,N'-dimethyl-N,N'-di-t-butyl-p-phenylenediamine.

[0247] Examples of hydroquinone include 2,5-di-t-octylhydroquinone, 2,6-didodecylhydroquinone, 2-dodecylhydroquinone, 2-dodecyl-5-chlorohydroquinone, 2-t-octyl-5-methylhydroquinone, and 2-(2-octadecenyl)-5-methylhydroquinone.

[0248] Examples of the organic sulfur compounds include dilauryl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, and ditetradecyl-3,3'-thiodipropionate.

[0249] Examples of the organic phosphorus compound include triphenylphosphine, tri(nonylphenyl)phosphine, tri(dinonylphenyl)phosphine, tricresylphosphine, and tri(2,4-dibutylphenoxy)phosphine.

[0250] Examples of the plasticizer include phthalate esters, aliphatic dibasic acid esters, trimellitate esters, phosphate esters, and fatty acid esters.

[0251] Specifically, examples of phthalate esters include dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and diisodecyl phthalate.

[0252] Examples of the aliphatic dibasic acid ester include di-2-ethylhexyl adipate and 2-ethylhexyl sebacate.

[0253] Examples of trimellitic acid esters include tri-2-ethylhexyl trimellitate and trioctyl trimellitate.

[0254] Examples of the phosphate ester include triethyl phosphate, tri-2-ethylhexyl phosphate, and tricresyl phosphate.

[0255] The fatty acid ester may, for example, be butyl oleate.

[0256] Examples of the preservatives include organic nitrogen sulfur compound preservatives and organic sulfur halide preservatives.

[0257] Examples of reducing agents include reducing organic compounds such as ascorbic acid, tartaric acid, citric acid, glucose, and metal formaldehyde sulfoxylates, and reducing inorganic compounds such as sodium thiosulfate, sodium sulfite, sodium bisulfite, and sodium metabisulfite.

[0258] Examples of the organic solvent include ketone solvents [e.g., acetone and methyl ethyl ketone (hereinafter, abbreviated as MEK)], ester solvents (e.g., ethyl acetate and γ-butyrolactone), ether solvents (e.g., THF), amide solvents (e.g., N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-methylcaprolactam), alcohol solvents (e.g., isopropyl alcohol), and aromatic hydrocarbon solvents (e.g., toluene and xylene).

[0259] [Other ingredients] The toner according to an embodiment may contain other components, such as a release agent, a colorant, a charge control agent, an external additive, a flowability improver, a cleaning property improver, and a magnetic material.

[0260] (Release agent) The release agent is not particularly limited and can be appropriately selected from known ones.

[0261] Examples of wax and wax release agents include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, and wood wax rice wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusin; and petroleum waxes such as paraffin, microcrystalline, and petrolatum.

[0262] In addition to these natural waxes, synthetic hydrocarbon waxes such as Fischer-Tropsch wax, polyethylene, and polypropylene; synthetic waxes such as esters, ketones, and ethers; and the like.

[0263] Further, fatty acid amide compounds such as 12-hydroxystearic acid amide, stearic acid amide, phthalimide anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, copolymers of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups in their side chains may be used.

[0264] Among these, hydrocarbon waxes such as paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, and polypropylene wax are preferred.

[0265] The melting point of the release agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 60° C. or more and 80° C. or less. If the melting point is less than 60° C., the release agent is likely to melt at low temperatures, and the heat resistance storage stability may be poor. If the melting point is more than 80° C., even if the resin melts and is in the fixing temperature range, the release agent may not melt sufficiently, causing fixing offset and image defects.

[0266] The content of the release agent is not particularly limited and can be appropriately selected according to the purpose, but is preferably 2 to 10 parts by mass, more preferably 3 to 8 parts by mass, relative to 100 parts by mass of the toner. If the content is less than 2 parts by mass, the high-temperature offset resistance and low-temperature fixability during fixing may be poor, and if it exceeds 10 parts by mass, the heat-resistant storage stability may decrease and image fogging may easily occur. If the content is within the above more preferred range, it is advantageous in terms of improving image quality and fixing stability.

[0267] (Coloring agent) The colorant is not particularly limited and can be appropriately selected depending on the purpose. Examples of the colorant include carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, and anthrazan yellow BGL. , Isoindolinone Yellow, Bengala, Red Lead, Cinnabar, Cadmium Red, Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Kanmin BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belkan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Carmine 6B, Pigment Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Examples of such pigments include malachite green lake, phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, and lithopone.

[0268] The content of the colorant is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 to 15 parts by mass, and more preferably 3 to 10 parts by mass, per 100 parts by mass of the toner.

[0269] The colorant can also be used as a masterbatch composited with a resin. Examples of resins to be produced by the masterbatch or kneaded with the masterbatch include, in addition to polyester resins, styrene or its substituted polymers such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; styrene-p-chlorostyrene copolymers, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, Styrene-based copolymers such as styrene-acrylonitrile copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-acrylonitrile-indene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester, epoxy resins, epoxy polyol resins, polyurethane, polyamide, polyvinyl butyral, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic or alicyclic hydrocarbon resins, aromatic petroleum resins, chlorinated paraffin, and paraffin wax. These may be used alone or in combination of two or more.

[0270] The master batch can be obtained by mixing and kneading the resin for the master batch and the colorant under high shear force. In this case, an organic solvent can be used to enhance the interaction between the colorant and the resin. In addition, a method called the flushing method, in which an aqueous paste containing water of the colorant is mixed and kneaded with the resin and the organic solvent, the colorant is transferred to the resin side, and the water and organic solvent components are removed, is also preferably used because the wet cake of the colorant can be used as it is and does not need to be dried. A high shear dispersing device such as a three-roll mill is preferably used for mixing and kneading.

[0271] (Charge control agent) The charge control agent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the charge control agent include nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, metal salicylic acid salts, and metal salts of salicylic acid derivatives.

[0272] Specific examples include the nigrosine dye Bontron 03, the quaternary ammonium salt Bontron P-51, the metal-containing azo dye Bontron S-34, the oxynaphthoic acid metal complex E-82, the salicylic acid metal complex E-84, and the phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.), the quaternary ammonium salt molybdenum complexes TP-302 and TP-415 (both manufactured by Hodogaya Chemical Co., Ltd.), LRA-901, the boron complex LR-147 (manufactured by Nippon Carlit Co., Ltd.), copper phthalocyanine, perylene, quinacridone, azo pigments, and other polymeric compounds having functional groups such as sulfonic acid groups, carboxyl groups, and quaternary ammonium salts.

[0273] The content of the charge control agent is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the toner. If the content exceeds 10 parts by mass, the chargeability of the toner is too high, the effect of the main charge control agent is reduced, and the electrostatic attraction force with the developing roller increases, which may lead to a decrease in the fluidity of the developer and a decrease in image density. These charge control agents can be melt-kneaded together with the master batch and resin and then dissolved and dispersed, or of course they can be added when directly dissolved and dispersed in an organic solvent, or they can be fixed on the toner surface after the toner particles are produced.

[0274] (External additives) As the external additive, inorganic fine particles and hydrophobized inorganic fine particles can be used in combination with the oxide fine particles. The average particle size of the hydrophobized primary particles is preferably 1 nm to 100 nm, and inorganic fine particles of 5 nm to 70 nm are more preferable.

[0275] It is also preferred that the hydrophobized inorganic particles contain at least one type of inorganic particles having an average primary particle size of 20 nm or less, and at least one type of inorganic particles having an average primary particle size of 30 nm or more. 2 / g~500m 2 It is preferable that the molecular weight is 1 / g.

[0276] The external additive is not particularly limited and can be appropriately selected depending on the purpose. Examples of the external additive include silica fine particles, hydrophobic silica, fatty acid metal salts (e.g., zinc stearate, aluminum stearate, etc.), metal oxides (e.g., titania, alumina, tin oxide, antimony oxide, etc.), fluoropolymers, etc.

[0277] Suitable additives include hydrophobized silica, titania, titanium oxide, and alumina fine particles. Examples of silica fine particles include R972, R974, RX200, RY200, R202, R805, and R812 (all manufactured by Nippon Aerosil Co., Ltd.). Examples of titania fine particles include P-25 (manufactured by Nippon Aerosil Co., Ltd.), STT-30, and STT-65C-S (all manufactured by Titanium Industries Co., Ltd.), TAF-140 (manufactured by Fuji Titanium Industries Co., Ltd.), MT-150W, MT-500B, MT-600B, and MT-150A (all manufactured by Teika Co., Ltd.).

[0278] Examples of hydrophobically treated titanium oxide particles include T-805 (manufactured by Nippon Aerosil Co., Ltd.), STT-30A, STT-65S-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-500T, TAF-1500T (all manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-100S, MT-100T (all manufactured by Teika Corporation), and IT-S (manufactured by Ishihara Sangyo Kaisha, Ltd.).

[0279] Hydrophobized oxide fine particles, hydrophobized silica fine particles, hydrophobized titania fine particles, and hydrophobized alumina fine particles can be obtained, for example, by treating hydrophilic fine particles with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, octyltrimethoxysilane, etc. Silicone oil-treated oxide fine particles and inorganic fine particles, which are treated with silicone oil by heating if necessary, are also suitable.

[0280] Examples of silicone oils include dimethyl silicone oil, methylphenyl silicone oil, chlorophenyl silicone oil, methylhydrogen silicone oil, alkyl-modified silicone oil, fluorine-modified silicone oil, polyether-modified silicone oil, alcohol-modified silicone oil, amino-modified silicone oil, epoxy-modified silicone oil, epoxy-polyether-modified silicone oil, phenol-modified silicone oil, carboxyl-modified silicone oil, mercapto-modified silicone oil, methacryl-modified silicone oil, and α-methylstyrene-modified silicone oil.

[0281] Examples of inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, silicon nitride, etc. Among these, silica and titanium dioxide are particularly preferred.

[0282] The content of the external additive is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 to 5 parts by mass, and more preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the toner.

[0283] The average particle size of the primary particles of the inorganic fine particles is not particularly limited and can be appropriately selected according to the purpose, but is preferably 100 nm or less, more preferably 3 nm to 70 nm. If it is smaller than this range, the inorganic fine particles are buried in the toner and their function is not effectively exerted. If it is larger than this range, the photoconductor surface is damaged unevenly, which is not preferable.

[0284] (Flow improver) The flowability improver is not particularly limited as long as it is capable of performing a surface treatment to increase hydrophobicity and prevent deterioration of flowability and charging properties even under high humidity, and can be appropriately selected according to the purpose, and examples thereof include silane coupling agents, silylating agents, silane coupling agents having a fluorinated alkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, modified silicone oils, etc. It is particularly preferable to perform a surface treatment of silica and titanium oxide with such a flowability improver and use them as hydrophobic silica and hydrophobic titanium oxide.

[0285] (Cleaning improver) The cleaning property improver is not particularly limited as long as it is added to the toner to remove the developer remaining on the photoconductor or primary transfer medium after transfer, and can be appropriately selected depending on the purpose, and examples thereof include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid, polymer fine particles produced by soap-free emulsion polymerization such as polymethyl methacrylate fine particles and polystyrene fine particles. The polymer fine particles preferably have a relatively narrow particle size distribution, and are preferably those having a volume average particle size of 0.01 μm to 1 μm.

[0286] (Magnetic material) The magnetic material is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include iron powder, magnetite, ferrite, etc. Among these, a white material is preferred in terms of color tone.

[0287] [Toner volume average particle size] The volume average particle diameter of the toner is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 3 μm or more and 7 μm or less, and the ratio of the volume average particle diameter to the number average particle diameter is preferably 1.2 or less.

[0288] <<Method of measuring particle size distribution>> The volume average particle diameter (D4) and number average particle diameter (Dn) of the toner, and the ratio thereof (D4 / Dn) can be measured using, for example, a Coulter Counter TA-II or a Coulter Multisizer II (both manufactured by Coulter, Inc.). In the present invention, a Coulter Multisizer II was used. The measurement method is described below.

[0289] First, 0.1 mL to 5 mL of a surfactant (preferably polyoxyethylene alkyl ether (nonionic surfactant)) is added as a dispersant to 100 mL to 150 mL of the electrolyte solution. Here, the electrolyte solution is a 1 mass % NaCl aqueous solution prepared using first-class sodium chloride, and for example, ISOTON-II (manufactured by Coulter) can be used. Then, 2 mg to 20 mg of a measurement sample is further added. The electrolyte solution in which the sample is suspended is subjected to a dispersion process for about 1 minute to 3 minutes using an ultrasonic disperser, and the volume and number of toner particles or toner are measured using a 100 μm aperture as an aperture with the above-mentioned measuring device, and the volume distribution and number distribution are calculated. From the obtained distribution, the volume average particle size (D4) and number average particle size (Dn) of the toner can be obtained.

[0290] As described above, the toner according to the embodiment includes a plurality of organic fine particles at least partially embedded in the surface of the toner base particle containing the crystalline polyester resin and the amorphous polyester resin. In the toner according to the embodiment, the standard deviation of the distance between adjacent organic fine particles not in contact with each other is 600 nm or less, and when the radius of the cross section of the toner is R, the area of ​​the crystalline polyester resin in the inner region of a perfect circle with a radius of R / 2 is less than 20% of the total area of ​​the crystalline polyester resin in the cross section, and the ratio of the crystalline polyester resin occupying the surface of the toner base particle is less than 15%. Since the ratio of the area of ​​the crystalline polyester resin in the inner region of a perfect circle with a radius of R / 2 to the total area of ​​the crystalline polyester resin in the cross section is within the above range, the toner can improve the image glossiness. In addition, since the ratio of the crystalline polyester resin occupying the surface of the toner base particle is within the above range, the toner can achieve both good low-temperature fixability and heat-resistant storage stability. In addition, since the standard deviation of the distance between adjacent organic fine particles is within the above range, the organic fine particles can be present in a scattered state on the surface of the toner base particle. Therefore, the toner can suppress the inhibition of low-temperature fixation of the toner by suppressing the exposure of the crystalline polyester resin, etc., and can improve the heat-resistant storage stability while ensuring low-temperature fixability. In addition, during cleaning, the inorganic fine particles liberated are easily accumulated on the contact surface between the cleaning blade and the photoconductor, and good cleaning properties can be exhibited.

[0291] Therefore, the toner according to one embodiment can have excellent low-temperature fixing properties, image gloss properties, and cleaning properties.

[0292] The toner according to an embodiment includes, in the toner base particles, one or more composite resins including a polycondensation resin and a styrene resin, and two polymerization resin components each having an independent reaction pathway are partially chemically bonded, and at least one of the two polymerization resin components includes an amorphous hybrid resin including a resin component of the same polymerization system as the polyester resin. This allows the crystalline polyester to be uniformly dispersed inside the toner base particles while suppressing exposure to the surface of the toner base particles. Therefore, the toner according to an embodiment can further improve low-temperature fixability and heat-resistant storage stability.

[0293] The toner according to one embodiment has a glass transition temperature Tg 1st The glass transition temperature Tg of the component of the toner that is insoluble in tetrahydrofuran at the first temperature rise in differential scanning calorimetry is 20°C to 50°C. 1st can be set to −40° C. to 10° C. As a result, the toner according to one embodiment can maintain low-temperature fixability and heat-resistant storage stability, and therefore the occurrence of blocking in a developing machine and filming on a photoconductor can be reduced.

[0294] <Toner manufacturing method> The method for producing the toner is not particularly limited and can be appropriately selected according to the purpose. The method for producing the toner preferably includes a granulation step of dispersing an oil phase containing a crystalline polyester resin and an amorphous polyester resin, and further containing a release agent, a colorant, etc., in an aqueous medium containing organic fine particles and an anionic surfactant containing a carboxyl group, to granulate the toner base particles, and at the same time, attaching the organic fine particles and the anionic surfactant containing a carboxyl group to the surface of the toner base particles.

[0295] In the toner manufacturing method according to an embodiment, in the granulation step, it is more preferable to use an oil phase containing a modified polyester, a hardener, and the like, in addition to a release agent and a colorant, as necessary.

[0296] The toner may be produced, for example, by a solution suspension method. For example, a method of producing toner base particles may be used in which an amorphous polyester resin is elongated by an elongation reaction and / or a crosslinking reaction between a prepolymer and a curing agent.

[0297] The method for producing toner base particles using this solution suspension method includes a step of preparing an aqueous medium (aqueous medium preparation step), a step of preparing an oil phase containing the toner materials (oil phase preparation step), a step of emulsifying or dispersing the toner materials (emulsifying or dispersing step), and a step of removing the organic solvent (organic solvent removal step).

[0298] (Preparation of aqueous medium) The aqueous medium (aqueous phase) can be prepared, for example, by dispersing resin particles, organic fine particles, and an anionic surfactant containing a carboxyl group in the aqueous medium. The amount of resin particles added to the aqueous medium is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0.5 parts by mass to 10 parts by mass with respect to 100 parts by mass of the aqueous medium.

[0299] The aqueous medium is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include water, a solvent miscible with water, and a mixture thereof. These may be used alone or in combination of two or more. Among these, water is preferred.

[0300] The solvent miscible with water can be appropriately selected depending on the purpose, and examples thereof include alcohol, lower ketones, dimethylformamide, tetrahydrofuran, cellosolves, etc. The alcohol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include methanol, isopropanol, ethylene glycol, etc. The lower ketones can be appropriately selected depending on the purpose, and examples thereof include acetone, methyl ethyl ketone, etc.

[0301] (Oil phase preparation process) The oil phase containing the toner materials includes a crystalline polyester resin, a non-crystalline polyester resin having at least one of a urethane bond and a urea bond, and a non-crystalline polyester resin having no urethane bond or urea bond, and further includes a curing agent, a releasing agent, a colorant, etc., as necessary, and can be prepared by dissolving or dispersing the toner materials in an organic solvent.

[0302] The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, but an organic solvent having a boiling point of less than 150° C. is preferred in terms of ease of removal.

[0303] The organic solvent having a boiling point of less than 150° C. is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, etc. These may be used alone or in combination of two or more.

[0304] Among these, ethyl acetate, toluene, xylene, benzene, methylene chloride, 1,2-dichloroethane, chloroform, carbon tetrachloride, etc. are preferable, and ethyl acetate is more preferable.

[0305] (Emulsification or dispersion process) The toner materials can be emulsified or dispersed by dispersing the oil phase containing the toner materials in an aqueous medium. At this time, organic fine particles can be arranged on the surface of the toner base particles, and an anionic surfactant containing a carboxyl group can be bound and arranged on the surface of the toner base particles.

[0306] Furthermore, when the toner materials are emulsified or dispersed, an elongation reaction and / or a crosslinking reaction occurs between the curing agent and the prepolymer, thereby producing an amorphous polyester resin.

[0307] The reaction conditions (reaction time, reaction temperature) for producing the prepolymer are not particularly limited, and can be appropriately selected depending on the combination of the curing agent and the prepolymer.

[0308] The reaction time is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 minutes to 40 hours, more preferably 2 hours to 24 hours.

[0309] The reaction temperature is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0°C to 150°C, more preferably 40°C to 98°C.

[0310] The method for stably forming a dispersion liquid containing a prepolymer in an aqueous medium is not particularly limited and may be appropriately selected depending on the purpose. For example, there is a method in which an oil phase prepared by dissolving or dispersing a toner material in a solvent is added to an aqueous medium phase, and the oil phase is dispersed by shear force.

[0311] The dispersing machine for dispersion is not particularly limited and can be appropriately selected depending on the purpose. Examples of the dispersing machine include a low-speed shear type dispersing machine, a high-speed shear type dispersing machine, a friction type dispersing machine, a high-pressure jet type dispersing machine, and an ultrasonic dispersing machine.

[0312] Among these, a high-speed shear type disperser is preferred because it is possible to control the particle size of the dispersion (oil droplets) to 2 μm to 20 μm.

[0313] When a high-speed shear type dispersing machine is used, the conditions such as the rotation speed, dispersing time, and dispersing temperature can be appropriately selected depending on the purpose.

[0314] The rotation speed is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1,000 rpm to 30,000 rpm, and more preferably 5,000 rpm to 20,000 rpm.

[0315] The dispersion time is not particularly limited and can be appropriately selected depending on the purpose, but in the case of a batch method, it is preferably 0.1 to 5 minutes.

[0316] The dispersion temperature is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0° C. to 150° C. under pressure, and more preferably 40° C. to 98° C. In general, the higher the dispersion temperature, the easier the dispersion.

[0317] The amount of the aqueous medium used when emulsifying or dispersing the toner material is not particularly limited and can be appropriately selected according to the purpose, but is preferably 50 parts by mass to 2000 parts by mass, more preferably 100 parts by mass to 100 parts by mass of the toner material. If the amount of the aqueous medium used is less than 50 parts by mass, the dispersion state of the toner material may become poor, and toner base particles of a predetermined particle size may not be obtained. If the amount of the aqueous medium used is more than 2000 parts by mass, the production cost may increase.

[0318] When emulsifying or dispersing the oil phase containing the toner materials, it is preferable to use a dispersant from the viewpoints of stabilizing the dispersion such as oil droplets, forming a desired shape, and sharpening the particle size distribution.

[0319] The dispersant is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include surfactants, poorly water-soluble inorganic compound dispersants, polymer-based protective colloids, etc. These may be used alone or in combination of two or more. Among these, surfactants are preferred.

[0320] The surfactant is not particularly limited and can be appropriately selected depending on the purpose. For example, anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, etc. can be used.

[0321] The anionic surfactant is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include alkylbenzene sulfonate, α-olefin sulfonate, phosphate, etc. Among these, those having a fluoroalkyl group are preferred.

[0322] (Organic solvent removal process) Toner base particles are obtained by removing the organic solvent from the dispersion liquid such as the emulsified slurry. The method for removing the organic solvent from the dispersion liquid is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a method of gradually increasing the temperature of the entire reaction system to evaporate the organic solvent in the oil droplets, and a method of spraying the dispersion liquid in a dry atmosphere to remove the organic solvent in the oil droplets.

[0323] When the organic solvent is removed, toner base particles are formed. The toner base particles can be washed, dried, etc., and can further be classified, etc. Classification can be performed by removing fine particles in a liquid using a cyclone, decanter, centrifugal separation, etc., or the classification operation can be performed after drying.

[0324] (Cleaning process) In the washing step, the method for removing a part or all of the resin (a1) includes a method for removing a part or all of (a1) by a chemical method. Among the removal steps by chemical methods, a preferred method is a method in which an alkaline aqueous solution is added to and mixed with the toner base particles to dissolve a part or all of the resin (a1).

[0325] Examples of the alkali in the alkaline aqueous solution include hydroxides of alkali metals such as potassium hydroxide and sodium hydroxide, and ammonia, etc. From the viewpoint of easiness in dissolving the resin (a1), potassium hydroxide and sodium hydroxide are preferred.

[0326] The pH of the alkali contained in the alkaline aqueous solution is preferably 8-14, and more preferably 10-12.

[0327] In the washing step, the toner base particles and the alkaline aqueous solution can be mixed by, for example, dropping the alkaline aqueous solution into the toner base slurry under stirring. An acid aqueous solution may also be dropped to neutralize the mixture.

[0328] (External addition process) The obtained toner base particles may be mixed with an external additive, a charge control agent, etc. In this case, by applying a mechanical impact force, it is possible to suppress the particles of the external additive, etc. from being detached from the surface of the toner base particles.

[0329] The method of applying the mechanical impact force can be appropriately selected depending on the purpose, and examples thereof include a method of applying an impact force to the mixture using a blade rotating at high speed, a method of introducing the mixture into a high-speed air current to accelerate it, and causing particles to collide with each other or with an appropriate collision plate, etc.

[0330] The device used in the method of applying a mechanical impact force can be appropriately selected depending on the purpose, and examples include an Angmill (manufactured by Hosokawa Micron Corporation), a device obtained by modifying an I-type mill (manufactured by Japan Pneumatic Mfg. Co., Ltd.) to reduce the grinding air pressure, a Hybridization System (manufactured by Nara Machinery Works, Ltd.), a Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), an automatic mortar, and the like.

[0331] Next, the mixture is passed through a sieve of 250 mesh or more to remove coarse particles and aggregated particles, thereby obtaining the toner according to one embodiment.

[0332] <Developer> The developer according to an embodiment includes the toner according to an embodiment, and may include other appropriately selected components such as a carrier, as necessary. As a result, the developer according to an embodiment is excellent in transferability, chargeability, low-temperature fixability, heat-resistant storage stability, image gloss, and cleanability, and can stably form high-quality images.

[0333] The developer may be a one-component developer or a two-component developer. However, when used in high-speed printers that correspond to the recent improvements in information processing speed, a two-component developer is preferable from the viewpoint of improving the developer life.

[0334] When the toner according to one embodiment is used in a one-component developer, even if the toner is balanced, there is little variation in the particle size of the toner, there is little filming of the toner on the developing roller, and there is little melting of the toner to components such as blades that thin the toner layer, and good and stable developability and images can be obtained even with long-term stirring in the developing device.

[0335] When the toner according to the embodiment is used as a two-component developer, it can be mixed with a carrier and used as a developer. When the developer is used as a two-component developer, even if the toner is balanced over a long period of time, the particle size of the toner is less likely to fluctuate, and good and stable developability and images can be obtained even when the toner is stirred for a long period of time in a developing device.

[0336] The content of the carrier in the two-component developer can be appropriately selected depending on the purpose, but is preferably 90 parts by mass to 98 parts by mass, and more preferably 93 parts by mass to 97 parts by mass, relative to 100 parts by mass of the two-component developer.

[0337] The developer according to an embodiment can be suitably used for image formation by various known electrophotographic methods such as a magnetic one-component development method, a non-magnetic one-component development method, and a two-component development method.

[0338] [Career] The carrier is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the carrier has a core material and a resin layer (coating layer) that coats the core material.

[0339] (Core material) The material of the core material is not particularly limited and can be appropriately selected according to the purpose. For example, manganese-strontium-based material of 50 emu / g to 90 emu / g, manganese-magnesium-based material of 50 emu / g to 90 emu / g, etc. can be mentioned. In order to ensure image density, it is preferable to use high magnetization materials such as iron powder of 100 emu / g or more, magnetite of 75 emu / g to 120 emu / g. In addition, it is preferable to use low magnetization materials such as copper-zinc-based materials of 30 emu / g to 80 emu / g, because it can reduce the impact of the developer in a standing state on the photoconductor and is advantageous for high image quality. These materials may be used alone or in combination of two or more.

[0340] The volume average particle diameter of the core material is not particularly limited and can be appropriately selected according to the purpose, but is preferably 10 μm to 150 μm, more preferably 40 μm to 100 μm. If the volume average particle diameter is 10 μm or more, the amount of fine powder in the carrier increases, and the magnetization per particle decreases, which can effectively prevent the problem of carrier scattering. On the other hand, if it is 150 μm or less, the specific surface area decreases, which can cause toner scattering, and in full color with many solid parts, the problem of poor reproduction of the solid parts can be effectively prevented.

[0341] (Resin layer) The resin layer can contain a resin and other components as necessary. The resin used in the resin layer can be a known material that can impart the necessary electrostatic property. Specifically, it is preferable to use a silicone resin, an acrylic resin, or a combination of these. In addition, the composition for forming the resin layer preferably contains a silane coupling agent.

[0342] The average thickness of the resin layer is preferably 0.05 μm to 0.50 μm.

[0343] <Developer container> The developer storage container according to the embodiment stores the developer according to the embodiment. The developer storage container is not particularly limited and can be appropriately selected from known containers, and examples of the developer storage container include a container body and a cap.

[0344] The size, shape, structure, material, etc. of the container body are not particularly limited, but the shape is preferably cylindrical, etc., and the inner surface is formed with spiral irregularities so that the developer content can be transferred to the outlet side by rotating, and it is particularly preferred that a part or all of the spiral irregularities have a bellows function. Furthermore, the material is not particularly limited, but it is preferred that the material has good dimensional accuracy, and examples of such materials include resin materials such as polyester resin, polyethylene resin, polypropylene resin, polystyrene resin, polyvinyl chloride resin, polyacrylic acid, polycarbonate resin, ABS resin, and polyacetal resin.

[0345] The developer storage container is easy to store, transport, and the like, and has excellent handleability, and therefore can be detachably attached to an image forming apparatus, a process cartridge, and the like, which will be described later, and used for replenishing the developer.

[0346] <Toner storage unit> The toner storage unit according to the embodiment can store the toner according to the embodiment. The toner storage unit according to the embodiment refers to a unit having a function of storing toner and storing the toner. Here, examples of the toner storage unit include a toner storage container, a developing unit, and a process cartridge.

[0347] The toner storage container refers to a container that stores toner.

[0348] The developing device has a means for containing toner and developing the toner.

[0349] The process cartridge is a cartridge that integrates at least an electrostatic latent image carrier (also called an image carrier) and a developing means, contains toner, and is detachable from an image forming apparatus. The process cartridge may further include at least one selected from a charging means, an exposure means, a cleaning means, etc.

[0350] The toner storage unit according to the embodiment stores the toner according to the embodiment. By mounting the toner storage unit according to the embodiment on an image forming apparatus and forming an image, the toner storage unit according to the embodiment is used to form an image. Therefore, the toner storage unit according to the embodiment can exhibit excellent low-temperature fixing properties, heat-resistant storage properties, and cleaning properties, and can form an image with excellent image gloss.

[0351] <Image forming device> An image forming apparatus according to one embodiment has an electrostatic latent image carrier, an electrostatic latent image forming unit that forms an electrostatic latent image on the electrostatic latent image carrier, and a developing unit that develops the electrostatic latent image formed on the electrostatic latent image carrier with toner to form a toner image, and may further have other components as necessary.

[0352] More preferably, the image forming apparatus according to one embodiment includes, in addition to the electrostatic latent image carrier, electrostatic latent image forming unit, and developing unit described above, a transfer unit that transfers the toner image onto the recording medium, and a fixing unit that fixes the transferred image onto the surface of the recording medium.

[0353] In the developing section, the toner according to the embodiment is used. Preferably, a developer containing the toner according to the embodiment and, if necessary, other components such as a carrier may be used to form a toner image.

[0354] (Electrostatic latent image carrier) The material, shape, structure, size, etc. of the electrostatic latent image carrier (sometimes called "electrophotographic photoreceptor" or "photoreceptor") are not particularly limited and can be appropriately selected from known materials. Examples of materials for the electrostatic latent image carrier include inorganic photoreceptors such as amorphous silicon and selenium, and organic photoreceptors (OPC) such as polysilane and phthalopolymethine. Among these, amorphous silicon is preferred in terms of long life.

[0355] As the amorphous silicon photoreceptor, for example, a photoreceptor having a photoconductive layer made of a-Si formed on the support by heating the support to 50° C. to 400° C. and forming a film on the support by a vacuum deposition method, a sputtering method, an ion plating method, a thermal CVD (chemical vapor deposition) method, a photo CVD method, a plasma CVD method, etc. Among these, the plasma CVD method, that is, a method in which a raw material gas is decomposed by a direct current, a high frequency wave, or a microwave glow discharge to form an a-Si deposition film on the support, is preferable.

[0356] The shape of the electrostatic latent image carrier is not particularly limited and can be appropriately selected depending on the purpose, but is preferably cylindrical. The outer diameter of the cylindrical electrostatic latent image carrier is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 3 mm to 100 mm, more preferably 5 mm to 50 mm, and particularly preferably 10 mm to 30 mm.

[0357] (Electrostatic latent image forming section) The electrostatic latent image forming unit is not particularly limited as long as it is a means for forming an electrostatic latent image on an electrostatic latent image carrier, and can be appropriately selected according to the purpose. The electrostatic latent image forming unit includes, for example, a charging member (charger) that uniformly charges the surface of the electrostatic latent image carrier, and an exposure member (exposure device) that imagewise exposes the surface of the electrostatic latent image carrier.

[0358] The charger is not particularly limited and can be appropriately selected depending on the purpose. Examples of the charger include a contact charger equipped with a conductive or semiconductive roll, brush, film, rubber blade, etc., and a non-contact charger that utilizes corona discharge such as a corotron or scorotron.

[0359] The shape of the charger may be any shape, such as a roller, a magnetic brush, a fur brush, etc., and can be selected according to the specifications and shape of the image forming apparatus.

[0360] The charger is preferably one that is arranged in contact or non-contact with the electrostatic latent image carrier and charges the surface of the electrostatic latent image carrier by applying superimposed DC and AC voltages to the electrostatic latent image carrier. Also, the charger is preferably a charging roller that is arranged in close proximity to the electrostatic latent image carrier in a non-contact manner via a gap tape and charges the surface of the electrostatic latent image carrier by applying superimposed DC and AC voltages to the charging roller.

[0361] The charger is not limited to a contact type charger, but it is preferable to use a contact type charging member since it provides an image forming apparatus in which the amount of ozone generated from the charger is reduced.

[0362] The exposure device is not particularly limited as long as it can expose the surface of the electrostatic latent image carrier charged by the charger in the shape of an image to be formed, and can be appropriately selected depending on the purpose. Examples of the exposure device include various exposure devices such as a copying optical system, a rod lens array system, a laser optical system, and a liquid crystal shutter optical system.

[0363] The light source used in the exposure device is not particularly limited and can be appropriately selected depending on the purpose. Examples of the light source include fluorescent lamps, tungsten lamps, halogen lamps, mercury lamps, sodium lamps, light-emitting diodes (LEDs), semiconductor lasers (LDs), electroluminescence (EL), and other light-emitting materials in general.

[0364] In order to irradiate only light in a desired wavelength range, various filters such as a sharp cut filter, a band pass filter, a near infrared cut filter, a dichroic filter, an interference filter, and a color temperature conversion filter can be used.

[0365] It is also possible to employ a backlight system in which exposure is performed imagewise from the back side of the electrostatic latent image bearing member.

[0366] (Developing section) The developing unit is not particularly limited as long as it can develop the electrostatic latent image formed on the electrostatic latent image carrier to form a visible image, and can be appropriately selected according to the purpose. For example, the developing unit can be suitably used one that contains toner and has a developing device that can apply the toner to the electrostatic latent image in a contact or non-contact manner, and a developing device equipped with a toner container is preferable.

[0367] The developing device may be a single-color developing device or a multi-color developing device. As the developing device, for example, a developing device having an agitator that frictionally agitates the toner to charge it, a magnetic field generating unit fixed inside, and a rotatable developer carrier that carries a developer containing toner on its surface is preferable.

[0368] (Transfer section) The transfer section preferably has a first transfer section that transfers a visible image onto an intermediate transfer body to form a composite transfer image, and a second transfer section that transfers the composite transfer image onto a recording medium. The intermediate transfer body is not particularly limited and can be appropriately selected from known transfer bodies depending on the purpose, and a transfer belt or the like is preferably used.

[0369] The transfer section (first transfer means and secondary transfer section) preferably has at least a transfer device that peels and charges a visible image formed on an electrostatic latent image carrier (photoconductor) onto a recording medium. The number of transfer sections may be one or more.

[0370] Examples of the transfer device include a corona transfer device using corona discharge, a transfer belt, a transfer roller, a pressure transfer roller, and an adhesive transfer device.

[0371] The recording medium is typically plain paper, but there are no particular limitations as long as it is capable of transferring the unfixed image after development, and it can be selected appropriately according to the purpose. A PET base for overhead projectors can also be used.

[0372] (Fixing part) The fixing unit is not particularly limited and can be appropriately selected depending on the purpose, but a known heating and pressing unit is suitable. Examples of the heating and pressing unit include a combination of a heating roller and a pressure roller, and a combination of a heating roller, a pressure roller, and an endless belt.

[0373] The fixing section is preferably a heating and pressurizing section having a heating element having a heat generating element, a film in contact with the heating element, and a pressure member in pressure contact with the heating element via the film, and capable of heat-fixing the recording medium on which an unfixed image has been formed by passing the recording medium between the film and the pressure member.

[0374] The heating temperature in the heating and pressurizing section is usually preferably 80°C to 200°C.

[0375] The surface pressure in the heating and pressing section is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 10 N / cm 2 ~80N / cm 2 It is preferable that:

[0376] In this embodiment, depending on the purpose, for example, a known optical fixing device may be used together with or instead of the fixing unit.

[0377] (others) The image forming apparatus according to the first embodiment may further include, for example, a static eliminator, a recycle unit, a controller, and the like.

[0378] ((Static charge removal section)) The charge removing section is not particularly limited as long as it can apply a charge removing bias to the electrostatic latent image bearing member, and can be appropriately selected from among known charge removers. For example, a charge removing lamp or the like is preferably used.

[0379] (Cleaning Department) The cleaning unit may be any type capable of removing the toner remaining on the electrostatic latent image carrier, and may be appropriately selected from among known cleaners. Examples of the cleaning unit include a magnetic brush cleaner, an electrostatic brush cleaner, a magnetic roller cleaner, a blade cleaner, a brush cleaner, and a web cleaner.

[0380] The image forming apparatus according to the first embodiment has a cleaning section, which improves the cleaning performance. That is, by controlling the adhesion between toner particles, the fluidity of the toner is controlled, and the cleaning performance can be improved. In addition, by controlling the characteristics of the toner after deterioration, it is possible to maintain excellent cleaning quality even under severe conditions such as a long life or high temperature and humidity. Furthermore, since the external additive can be sufficiently liberated from the toner on the photoreceptor, a deposition layer (dam layer) of the external additive in the cleaning blade nip can be formed, thereby achieving high cleaning performance.

[0381] (Recycling Department) The recycling section is not particularly limited, and examples thereof include known conveying means.

[0382] ((Control Unit)) The control unit can control the movement of each of the above-mentioned parts. The control unit is not particularly limited as long as it can control the movement of each of the above-mentioned parts, and can be appropriately selected depending on the purpose. For example, the control unit can be a control device such as a sequencer or a computer.

[0383] The image forming apparatus according to one embodiment can form images using the toner according to one embodiment, and therefore can exhibit excellent low-temperature fixing properties, heat-resistant storage properties, and cleaning properties, and can form images with excellent image gloss.

[0384] <Image forming method> An image forming method according to an embodiment includes an electrostatic latent image forming step of forming an electrostatic latent image on an electrostatic latent image carrier, and a developing step of developing the electrostatic latent image with toner to form a toner image, and may further include other steps as necessary. The image forming method can be suitably performed by the image forming apparatus, the electrostatic latent image forming step can be suitably performed by the electrostatic latent image forming unit, the developing step can be suitably performed by the developing unit, and the other steps can be suitably performed by the other units.

[0385] Furthermore, the image forming method according to one embodiment more preferably includes, in addition to the electrostatic latent image forming process and the developing process described above, a transfer process of transferring the toner image onto a recording medium, and a fixing process of fixing the transferred image onto the surface of the recording medium.

[0386] In the developing step, the toner according to an embodiment is used. Preferably, a developer containing the toner according to an embodiment and, if necessary, other components such as a carrier may be used to form a toner image.

[0387] The electrostatic latent image forming process is a process of forming an electrostatic latent image on an electrostatic latent image carrier, and includes a charging process of charging the surface of the electrostatic latent image carrier and an exposure process of exposing the charged surface of the electrostatic latent image carrier to light to form an electrostatic latent image. Charging can be performed, for example, by applying a voltage to the surface of the electrostatic latent image carrier using a charger. Exposure can be performed, for example, by exposing the surface of the electrostatic latent image carrier to light in an imagewise manner using an exposure device. The electrostatic latent image can be formed, for example, by uniformly charging the surface of the electrostatic latent image carrier and then exposing it to light in an imagewise manner, and can be performed by an electrostatic latent image forming unit.

[0388] The developing process is a process in which the electrostatic latent image is successively developed with toners of multiple colors to form a visible image. The visible image can be formed, for example, by developing the electrostatic latent image with toners, and can be performed by a developing device.

[0389] In the developing device, for example, toner and carrier are mixed and stirred, and the toner becomes charged by friction during this process and is held in a standing state on the surface of the rotating magnet roller, forming a magnetic brush. Since the magnet roller is disposed near an electrostatic latent image carrier (photoconductor), a part of the toner constituting the magnetic brush formed on the surface of the magnet roller moves to the surface of the electrostatic latent image carrier (photoconductor) by electrical attraction. As a result, the electrostatic latent image is developed by the toner, and a visible image made of the toner is formed on the surface of the electrostatic latent image carrier (photoconductor).

[0390] The transfer step is a step of transferring a visible image to a recording medium. The transfer step is preferably performed using an intermediate transfer body, and after the visible image is primarily transferred onto the intermediate transfer body, the visible image is secondarily transferred onto the recording medium. The transfer step is more preferably performed using toner of two or more colors, preferably full-color toner, and includes a primary transfer step of transferring the visible image onto the intermediate transfer body to form a composite transfer image, and a secondary transfer step of transferring the composite transfer image onto the recording medium. The transfer can be performed, for example, by charging an electrostatic latent image carrier (photoconductor) with a transfer charger, and can be performed by a transfer section.

[0391] The fixing process is a process in which the visible image transferred to the recording medium is fixed using a fixing device, and may be performed for each color developer each time it is transferred to the recording medium, or may be performed simultaneously for each color developer in a stacked state.

[0392] The image forming method according to the first embodiment may further include other steps appropriately selected as necessary, such as a static elimination step, a cleaning step, a recycling step, and the like.

[0393] The charge removing step is a step of removing electricity by applying a charge removing bias to the electrostatic latent image bearing member, and can be suitably performed by the charge removing unit.

[0394] The cleaning step is a step of removing the toner remaining on the electrostatic latent image carrier, and can be suitably performed by a cleaning unit.

[0395] The recycling step is a step in which the toner removed in the cleaning step is recycled to the developing unit, and can be suitably carried out by the recycling unit.

[0396] The image forming method according to an embodiment can form an image using the toner according to an embodiment, and therefore can provide an image having excellent low-temperature fixing property, heat-resistant storage property, and cleaning property, as well as excellent image gloss.

[0397] [One embodiment of the image forming apparatus] One aspect of an image forming apparatus according to an embodiment will be described with reference to Fig. 5. The image forming apparatus is not particularly limited as long as it is an apparatus that forms an image using toner, such as a printer, a copier, a facsimile, or a multifunction machine, and Fig. 5 will be used to explain the case where the image forming apparatus of this embodiment is a printer.

[0398] 5 is a schematic diagram showing an example of an image forming apparatus according to an embodiment. As shown in FIG. 5, an electrophotographic image forming apparatus (printer) 1 includes a paper feed section 10, a conveyance section 20, an image forming section 30, a transfer section 40, a fixing section 50, and a toner cartridge 60.

[0399] The paper feed section 10 includes a paper feed cassette 11 in which paper P to be fed is stacked, and a paper feed roller 12 that feeds the paper P stacked in the paper feed cassette 11 one sheet at a time.

[0400] The paper feed cassettes 11 are disposed below the exposure unit 32. Each paper feed cassette 11 contains a stack of transfer paper P, which is a recording medium.

[0401] The paper feed roller 12 is disposed so as to come into contact with the topmost sheet of transfer paper P in the paper feed cassette 11 .

[0402] In the paper feed section 10, when the paper feed roller 12 is driven to rotate counterclockwise in the figure by the driving means, the topmost transfer sheet P in the paper feed cassette 11 is discharged from the right side of the paper feed cassette 11 in Figure 5 toward the conveying section 20. The discharged transfer sheet P is sandwiched between the rollers of the conveying roller 21 and conveyed from the bottom to the top in Figure 5.

[0403] The conveying section 20 includes a conveying roller 21 that conveys the transfer paper P fed by the paper feed roller 12 toward the transfer section 40, a pair of timing rollers 22 that hold the leading edge of the transfer paper P conveyed by the conveying roller 21 and wait, and send the paper to the transfer section 40 at a predetermined timing, a paper discharge roller 23 that discharges the paper P with the fixed color toner image onto a paper discharge tray 24, and a paper discharge tray 124 into which the paper P discharged from the paper discharge roller 23 is fed.

[0404] The transport rollers 21 are disposed so as to sandwich the transfer sheet P, and transport the transfer sheet P from the lower side to the upper side in FIG.

[0405] The timing roller 22 is disposed at the downstream end in the transport direction of the transport roller 21. As soon as the timing roller 22 sandwiches the transfer paper P sent from the transport roller 21 between the rollers, the timing roller 22 temporarily stops the rotation of both rollers. Then, the timing roller 22 sends the transfer paper P sandwiched between the rollers toward the secondary transfer nip at a timing that allows the transfer paper P to be synchronized with the four-color toner image on the intermediate transfer belt 43.

[0406] The paper discharge roller 23 is a roller that discharges the transfer paper P to the outside of the printer 100 after the fixing process has been performed.

[0407] The paper discharge tray 24 is provided on the upper surface of the housing of the printer 100 main body, and stacks the transfer paper P discharged to the outside of the printer 100 by the paper discharge rollers 23 .

[0408] The image forming section 30 includes four imaging units 31Y, 31C, 31M and 31K for yellow, magenta, cyan and black (hereinafter referred to as Y, C, M and K, respectively), and an exposure device 32 which is a latent image forming section.

[0409] The imaging units 31Y, 31C, 31M, and 31K are arranged in order from left to right in the drawing at a predetermined interval, and are arranged side by side so as to face the intermediate transfer belt 141. The imaging units 31Y, 31C, 31M, and 31K form images using developers containing Y toner, C toner, M toner, and K toner, respectively. The developers contain toner and carrier. The four imaging units 31Y, 31C, 31M, and 31K each use a different type of developer.

[0410] The configurations of the imaging units 31Y, 31C, 31M, and 31K will be described. Note that the imaging units 31Y, 31C, 31M, and 31K are similar except for the toner colors, so only the configuration of the imaging unit 31Y will be described, and the configurations of the other imaging units 31C, 31M, and 31K will not be described.

[0411] The imaging unit 31Y incorporates a drum-shaped photoconductor 311Y, a charging device 312Y, a developing device 313Y, a photoconductor cleaning device 314, a lubricant application device (not shown), a cleaning roller, a static electricity removal lamp, etc. into one unit as a process cartridge, which is detachable from the image forming apparatus 1. Around the photoconductor 11Y, the photoconductor 311Y, the charging device 312Y, the developing device 313Y, the photoconductor cleaning device 314, a lubricant application device (not shown), a cleaning roller, a static electricity removal lamp, etc. are arranged.

[0412] Although the photoconductor 311Y is shown to have a drum shape, it may also be in the form of a sheet or an endless belt.

[0413] The charging device 312Y may be a known device such as a corotron, a scorotron, or a solid-state charger. Of these charging methods, the contact charging method and the non-contact close-by arrangement method are more preferable, and have the advantages of increasing charging efficiency, reducing the amount of ozone generated, and enabling the device to be made smaller. In this embodiment, the charging device 312Y includes a charging roller 3121Y, which is a charging member, and uses a non-contact close-by arrangement method in which the charging roller 3121Y is placed close to the photoconductor 311Y at a predetermined distance and in a non-contact manner. The charging roller 3121Y is placed in a non-contact manner with the photoconductor 311Y, and charges the photoconductor 311Y to a predetermined polarity and a predetermined potential. The surface of the photoconductor 311Y, which is uniformly charged by the charging roller 3121Y, is irradiated with a laser beam L from the exposure device 32 based on image information, and an electrostatic latent image is formed.

[0414] The developing device 313Y converts the latent image formed on the surface of the photoconductor 311Y into a toner image. The developing device 313Y has a developing roller 3131Y as a developer carrier. A developing bias is applied to the developing roller 3131Y from a power source.

[0415] In the developing device 13Y, the toner in the developer is charged to a predetermined polarity. Then, the developer is pumped up onto the surface of the developing roller 3131Y, and the toner of the pumped up developer adheres to the latent image on the photoconductor 311Y in a developing area facing the photoconductor 311Y.

[0416] The photoconductor cleaning device 314 cleans the toner remaining on the photoconductor 311Y after the toner image is transferred to the intermediate transfer belt 43 included in the transfer unit 40. The photoconductor cleaning device 314Y may have a fur brush, a cleaning blade, or the like.

[0417] A lubricant application device (not shown) applies a lubricant onto the surface of the photoconductor 311Y after it has been cleaned by the photoconductor cleaning device 314Y.

[0418] The cleaning roller (not shown) cleans the charging roller 3121Y.

[0419] A charge removing lamp (not shown) removes the surface potential of the photoconductor 311Y after cleaning.

[0420] The exposure device 32 is disposed below the image forming unit 11. The exposure device 32 irradiates the photoconductors 311Y, 311C, 311M, and 311K with laser light L emitted based on image information. As a result, electrostatic latent images for Y, C, M, and K are formed on the photoconductors 311Y, 311C, 311M, and 311K.

[0421] The exposure unit 32 includes a polygon mirror 321 that is rotated by a motor to irradiate laser light L emitted from a light source onto photoconductors 311Y, 311C, 311M, and 311K via a plurality of optical lenses and mirrors while deflecting the laser light L by the polygon mirror 321. Note that the exposure unit 32 may include an LED array for optical scanning instead of the above configuration.

[0422] The light source for the laser light L of the exposure device 32 and the light source for the discharge lamp can be any light-emitting material such as a fluorescent lamp, a tungsten lamp, a halogen lamp, a mercury lamp, a sodium lamp, a light-emitting diode (LED), a semiconductor laser (LD), an electroluminescence (EL), etc.

[0423] In order to irradiate only light in a desired wavelength range, various filters such as a sharp cut filter, a band pass filter, a near infrared cut filter, a dichroic filter, an interference filter, and a color temperature conversion filter can be used.

[0424] Of these light sources, light emitting diodes and semiconductor lasers are preferably used since they have high irradiation energy and emit light with a long wavelength of 600 to 800 nm.

[0425] The transfer section 40 is disposed above the four image forming units 1Y, 1C, 1M, and 1K. The transfer section 40 includes a drive roller 41, a driven roller 42, an intermediate transfer belt 43 that is an intermediate transfer body that can rotate counterclockwise in the figure as the drive roller 41 is driven, primary transfer rollers 44Y, 44C, 44M, and 44K that are provided facing the photoconductors 311Y, 311C, 311M, and 311K across the intermediate transfer belt 43, and a secondary opposing roller 45 and a secondary transfer roller 46 that are provided facing each other across the intermediate transfer belt 43 at a transfer position of the toner image to paper. The transfer section 40 transfers the toner images of each color formed on the surfaces of the photoconductors 311Y, 311C, 311M, and 311K onto the surface of the intermediate transfer belt 43 in a superimposed manner.

[0426] The driving roller 41 is a roller that drives the intermediate transfer belt 43 to rotate.

[0427] The driven roller 42 is disposed inside the intermediate transfer belt 43 and is a roller for moving the intermediate transfer belt 43 endlessly.

[0428] The intermediate transfer belt 43 is an endless belt that is stretched around seven rollers arranged on the inside, and is designed to be endlessly movable in the direction of the arrow by the rotational drive of the drive roller 41.

[0429] The primary transfer rollers 44Y, 44C, 44M, and 44K are primary transfer members provided in a primary transfer device that is a primary transfer section that transfers the toner images on the surfaces of the photoconductors 311Y, 311C, 311M, and 311K to the intermediate transfer belt 43. The primary transfer rollers 44Y, 44C, and 44M, and 44K sandwich the intermediate transfer belt 43 between the photoconductors 311Y, 311C, 311M, and 311K to form primary transfer nips. The primary transfer rollers 44Y, 44C, and 44M, and 44K apply a transfer bias of the opposite polarity (e.g., positive) to that of the toner to the back surface (inner peripheral surface of the loop) of the intermediate transfer belt 43. As the intermediate transfer belt 43 moves endlessly, the Y, C, M, and K toner images on the photoconductors 311Y, 311C, 311M, and 311K are sequentially passed through the primary transfer nips for Y, C, M, and K, and are primarily transferred in a superimposed manner onto the surface of the intermediate transfer belt 43. As a result, a four-color superimposed toner image (hereinafter referred to as a four-color toner image) is formed on the intermediate transfer belt 43.

[0430] The secondary opposing roller 45 sandwiches the intermediate transfer belt 43 with a secondary transfer roller 46 disposed outside the loop of the intermediate transfer belt 43 to form a secondary transfer nip.

[0431] A secondary transfer bias is applied to the secondary transfer roller 46. The secondary transfer roller 46 is a secondary transfer member that performs secondary transfer of the four-color toner image on the intermediate transfer belt 43 all at once onto the transfer paper P. The four-color toner image on the intermediate transfer belt 43 is secondarily transferred all at once onto the transfer paper P in the secondary transfer nip due to the influence of the secondary transfer electric field and nip pressure formed between the secondary transfer roller 46 and the secondary opposing roller 45. This results in a color toner image.

[0432] After passing through the secondary transfer nip, residual toner that has not been transferred to the transfer paper P adheres to the intermediate transfer belt 43. The residual toner is cleaned by a belt cleaning unit (not shown).

[0433] When forming a monochrome image, the printer 100 revolves the primary transfer rollers 44Y, 44C, 44M, 44K for Y, C, and M counterclockwise around the rotation axis of the driven roller 42 to separate the intermediate transfer belt 21 from the photoconductors 311Y, 311C, and 311M for Y, C, and M. Then, of the four imaging units 31Y, 31C, 31M, and 31K, only the imaging unit 31K for K is driven to form a monochrome image. This makes it possible to avoid wear and tear on the members constituting the imaging units due to unnecessary driving of the imaging units 31Y, 31C, and 31M when forming a monochrome image.

[0434] The fixing section 50 is disposed above the secondary transfer nip in the drawing. The fixing section 50 includes a fixing belt unit 51 that contains a heat source such as a halogen lamp and heats the transfer paper P, and a pressure roller 52 that rotatably presses the fixing belt unit 51 to form a fixing nip in contact with the fixing belt 621.

[0435] The transfer paper P that has passed through the secondary transfer nip described above is separated from the intermediate transfer belt 43 and then sent into the fixing section 50. Then, in the process of being conveyed from the bottom to the top in the figure while being sandwiched in the fixing nip inside the fixing section 50, the transfer paper P is heated and pressed by the fixing belt unit 51, so that heat and pressure are applied to the color toner image on the transfer paper P, and the color toner image is fixed to the transfer paper P.

[0436] The transfer paper P which has been subjected to the fixing process in this manner passes between the rollers of the paper discharge roller 23, and is then discharged onto the paper discharge tray 24. This completes a series of image forming processes.

[0437] The toner cartridge 60 is provided above the transfer unit 40 and includes toner cartridges 60Y, 60C, 60M, and 60K. The toner cartridges 60Y, 60C, 60M, and 60K accommodate Y, C, M, and K toners, respectively. The Y, C, M, and K toners in the toner cartridges 60Y, 60C, 60M, and 60K are appropriately supplied to the developing devices 313Y, 313C, 313M, and 313K of the image forming units 31Y, 31C, 31M, and 31K. These toner cartridges 60Y, 60C, 60M, and 60K are detachable from the printer body independently of the image forming units 31Y, 31C, 31M, and 31K.

[0438] <Process cartridge> The process cartridge according to one embodiment is molded so as to be detachably attached to various image forming devices, and has an electrostatic latent image carrier that carries an electrostatic latent image, and a developing unit that develops the electrostatic latent image carried on the electrostatic latent image carrier with a developer according to the above-mentioned one embodiment to form a toner image, and may have other configurations as necessary.

[0439] The electrostatic latent image carrier is the same as the electrostatic latent image carrier of the image forming apparatus described above, and therefore details thereof will be omitted.

[0440] The developing unit includes a developer container that contains the developer according to an embodiment, and a developer carrier that carries and transports the developer contained in the developer container. The developing unit may further include a regulating member or the like to regulate the thickness of the developer carried by the developer container.

[0441] FIG. 6 shows an example of a process cartridge according to an embodiment. As shown in FIG. 6, the process cartridge 200 has a photoconductor drum 210, a corona charger 220 as a charging unit, a developing device 230, a transfer roller 240, and a cleaning device 250. An exposure device 260 is provided above the process cartridge 200. These members constituting the process cartridge 200 are the same as the photoconductors 311Y, 311C, 311M, and 311K, the charging devices 312Y, 312C, 312M, and 312K, the developing devices 313Y, 313C, 313M, and 313K, the photoconductor cleaning devices 314, 314C, 314M, and 314K, and the primary transfer rollers 44Y, 44C, 44M, and 44K shown in FIG. 5, so details are omitted.

[0442] In the process cartridge 200, the surface of the photosensitive drum 210 is uniformly charged using a corona charger 220, and after the surface of the photosensitive drum 210 is uniformly charged, the exposure device 260 is used to expose the photosensitive drum 210 to exposure light L to form an electrostatic latent image. The electrostatic latent image formed on the photosensitive drum 210 is then developed with toner supplied from a developing device 230 to form a toner image. The toner image formed on the photosensitive drum 210 is then transferred to the transfer paper P conveyed by the transfer roller 240 by a transfer bias applied by the roller. EXAMPLES

[0443] The embodiments will be described in more detail below with reference to examples and comparative examples, but the embodiments are not limited to these examples and comparative examples.

[0444] <Synthesis of amorphous polyester resin> [Production Example 1: Synthesis of amorphous polyester resin A] In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were charged. At this time, the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 85 / 15 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), the molar ratio of terephthalic acid and adipic acid was 75 / 25 (terephthalic acid / adipic acid), the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl group to carboxyl group, OH / COOH, was 1.2. The mixture of each component charged in the four-neck flask was then reacted with titanium tetraisopropoxide (500 ppm relative to the resin component) at normal pressure at 230°C for 8 hours, and then further reacted at a reduced pressure of 10 mmHg to 15 mmHg for 4 hours. Trimellitic anhydride was then added to the reaction vessel so that the amount was 1 mol% relative to the total resin component, and reacted at 180°C and normal pressure for 3 hours. As a result, amorphous polyester resin A was obtained.

[0445] [Production Example 2: Synthesis of amorphous polyester resin B] In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added, and the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 85 / 15 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the terephthalic acid and adipic acid were The molar ratio (terephthalic acid / adipic acid) was 65 / 35, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C and normal pressure for 3 hours to obtain amorphous polyester resin B.

[0446] [Production Example 3: Synthesis of amorphous polyester resin C] In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, bisphenol A ethylene oxide side 2 mole adduct, bisphenol A propylene oxide 3 mole adduct, terephthalic acid, adipic acid, and trimethylolpropane were added, and the molar ratio of bisphenol A ethylene oxide side 2 mole adduct and bisphenol A propylene oxide 3 mole adduct was 85 / 15 (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct), and the terephthalic acid and adipic acid were The molar ratio (terephthalic acid / adipic acid) was 60 / 40, the amount of trimethylolpropane in the total monomers was 1 mol%, and the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.2. The mixture was reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components, and the mixture was reacted at 180°C and normal pressure for 3 hours to obtain amorphous polyester resin C.

[0447] <Preparation of Crystalline Polyester Resin Dispersion> [Synthesis of crystalline polyester resin] Sebacic acid and 1,6-hexanediol were charged into a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 0.9. The mixture of the components charged into the four-neck flask was then reacted with titanium tetraisopropoxide (500 ppm relative to the resin components) at 180°C for 10 hours. The mixture was then heated to 200°C and reacted for 3 hours, and further reacted at a pressure of 8.3 kPa for 2 hours. As a result, crystalline polyester resin 1 was obtained.

[0448] [Preparation of crystalline polyester dispersion] In a container equipped with a stirring rod and a thermometer, 60 parts by mass of crystalline polyester resin 1 and 400 parts by mass of ethyl acetate were charged, and the temperature was raised to 80°C while stirring, and the temperature was maintained at 80°C for 5 hours. The mixed liquid in the container was then cooled to 30°C in 1 hour, and dispersed using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.) at a liquid delivery rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, and 80% by volume of zirconia beads with a diameter of 0.5 mm, with 3 passes. As a result, crystalline polyester resin dispersion 1 was obtained.

[0449] <Synthesis of prepolymer> [Production Example 1: Synthesis of Prepolymer A] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were charged together with titanium tetraisopropoxide (1,000 ppm relative to the resin component). At this time, the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the composition of the diol component was 100 mol% of 3-methyl-1,5-pentanediol, the composition of the dicarboxylic acid component was 40 mol% of isophthalic acid and 60 mol% of adipic acid, and the amount of trimellitic anhydride in the total monomers was 1 mol%. After that, the mixture was heated to 200°C in about 4 hours, and then heated to 230°C in 2 hours, and the reaction was carried out until no water was discharged. After that, the reaction was further carried out for 5 hours under a reduced pressure of 10 mmHg to 15 mmHg. As a result, intermediate polyester A was obtained.

[0450] Next, intermediate polyester A and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, and diluted with ethyl acetate to a 50% ethyl acetate solution. The mixture was then reacted at 100°C for 5 hours to obtain prepolymer A.

[0451] [Production Example 2: Synthesis of Prepolymer B] Into a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 3-methyl-1,5-pentanediol, isophthalic acid, adipic acid, and trimellitic anhydride were added together with titanium tetraisopropoxide (1,000 ppm relative to the resin component) so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.5, the diol component was 100 mol% 3-methyl-1,5-pentanediol, the dicarboxylic acid component was 67 mol% isophthalic acid and 33 mol% adipic acid, and the amount of trimellitic anhydride in all monomers was 1 mol%.

[0452] Thereafter, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged.

[0453] Thereafter, the reaction was continued for another 5 hours under a reduced pressure of 10 mmHg to 15 mmHg, and an intermediate polyester B was obtained.

[0454] Next, intermediate polyester B and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube in a molar ratio (isocyanate group of IPDI / hydroxyl group of intermediate polyester) of 2.0, diluted with ethyl acetate to become a 50% ethyl acetate solution, and reacted at 100°C for 5 hours to obtain prepolymer B.

[0455] <Synthesis of hybrid resin> In a 5L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple, 7.2g of 2,3-butanediol, 6.08g of 1,2-propanediol, 18.59g of terephthalic acid and 0.18g of tin(II) 2-ethylhexanoate were placed. Nitrogen gas was then introduced into the vessel to maintain an inert atmosphere and raise the temperature, and the vessel was then kept at 180°C for 1 hour. The vessel was then heated from 180°C to 230°C at a rate of 10°C / hr, and then subjected to a condensation polymerization reaction at 230°C for 10 hours. The reaction was then further carried out at 230°C and 8.0kPa for 1 hour. After cooling to 160°C, 0.6g of acrylic acid, 7.79g of styrene, 1.48g of 2-ethylhexyl acrylate and dibutyl peroxide were added dropwise using a dropping funnel over 1 hour. After the addition, the vessel was kept at 160°C and the addition polymerization reaction was aged for 1 hour. Thereafter, the mixture in the container was heated to 210°C, 4.61g of trimellitic anhydride was added to the container, and the reaction was carried out at 210°C for 2 hours. The reaction was carried out at 210°C and 10kPa until the desired softening point was reached. In this way, amorphous hybrid resin 1 was obtained. The SP value of the obtained amorphous hybrid resin 1 was 10.8. The weight average molecular weight of amorphous hybrid resin 1 was 55000, the number average molecular weight was 2800, the glass transition temperature Tg was 55°C, and the acid value was 9.4mgKOH / g.

[0456] <Synthesis of organic particles> [Production Example 1: Production of microparticle dispersion (W0-1) containing organic microparticles (A)] In a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, 3760 parts by mass of water and 150 parts by mass of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged, and the mixture was homogenized by stirring at 200 rpm. After the mixture was heated to raise the temperature inside the system to 75°C, 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added to the mixture, and then a mixture consisting of 430 parts by mass of styrene, 270 parts by mass of butyl acrylate, and 300 parts by mass of methacrylic acid was dropped over 4 hours. After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a fine particle dispersion (W0-1) containing organic fine particles (A) consisting of a resin (a1-1) which is a polymer in which styrene, butyl acrylate, and methacrylic acid are copolymerized with polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium.

[0457] The volume average particle diameter of the microparticles in the microparticle dispersion (W0-1) was 30 nm. The volume average particle diameter was measured using a laser Doppler particle size distribution measuring device (nanotrac UPA-150EX, manufactured by Nikkiso Co., Ltd.).

[0458] A part of the fine particle dispersion (W0-1) was dried to isolate the resin (a1-1) which was the organic fine particles (A). The glass transition temperature Tg of the resin (a1-1) was 53° C., and the acid value was 195 mg KOH / g.

[0459] [Production Example 2: Production of microparticle dispersion (W-1) containing organic microparticles (A-1)] Next, 667 parts by mass of the microparticle dispersion (W0-1) and 248 parts by mass of water were charged into a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corp.) was added, and the temperature in the system was raised to 70°C by heating. Then, 43.3 parts by mass of styrene, 23.3 parts by mass of butyl acrylate, and 18.0 parts by mass of 1% by mass aqueous ascorbic acid solution were dropped into the mixed liquid over 2 hours. After the dropping, the mixed liquid was aged at 70°C for 4 hours to obtain a microparticle dispersion containing organic microparticles (A-1) consisting of resin microparticles containing resin (a2-1) and resin (a1-1) as constituent components in the same particle, which are polymers in which styrene and butyl acrylate are copolymerized, using the microparticles in the microparticle dispersion (W0-1) as seeds. Water was added to the obtained microparticle dispersion so that the solid concentration was 20%, and a microparticle dispersion (W-1) was obtained.

[0460] The volume average particle diameter of the organic fine particles (A-1) was 34.3 nm. The volume average particle diameter was measured in the same manner as for the organic fine particles (A) above.

[0461] The fine particle dispersion (W-1) was neutralized with 10% by weight aqueous ammonia to pH 9.0, and the precipitate was centrifuged and dried to isolate the resin (a2-1) from the organic fine particles (A-1). The glass transition temperature Tg of the resin (a2-1) was 53°C.

[0462] It was confirmed that the microparticle dispersion (W-1) contains organic microparticles (A-1) containing resin (a1-1) and resin (a2-1) as constituent components within the same particle by drying a portion of the microparticle dispersion (W-1) and isolating the organic microparticles (A-1), as in the above Production Example 1.

[0463] <Production of modified wax> In a pressure-resistant reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, and a dropping cylinder, 454 parts by mass of xylene and 150 parts by mass of low molecular weight polyethylene (Sanyo Chemical Industries, Sanwax LEL-400) were added and replaced with nitrogen. Then, the mixture was heated to 170°C under stirring, and a mixed solution of 595 parts by mass of styrene, 255 parts by mass of methyl methacrylate, 34 parts by mass of di-t-butylperoxyhexahydroterephthalate, and 119 parts by mass of xylene was dropped at the same temperature over 3 hours, and the mixture was maintained at the same temperature for 30 minutes. Next, the xylene was distilled off under a reduced pressure of 0.039 MPa to obtain modified wax 1.

[0464] The sp value of the graft chain of the obtained modified wax 1 was 10.35 (cal / cm 3 ) 1 / 2 The number average molecular weight Mn was 1,900, the weight average molecular weight Mw was 5,200, and the glass transition temperature Tg was 57°C.

[0465] <Toner manufacturing> [Example 1] (Preparation of Wax Dispersion) In a container equipped with a stirring rod and a thermometer, 50 parts by mass of paraffin wax (manufactured by Nippon Seiro Co., Ltd., HNP-9, hydrocarbon wax, melting point 75°C, SP value 8.8), 5 parts by mass of modified wax 1, and 165 parts by mass of ethyl acetate were charged, heated to 80°C under stirring, and held at 80°C for 5 hours. The mixture was then cooled to 30°C in 1 hour, and dispersed using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.) at a liquid delivery rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, and 80% by volume of 0.5 mm diameter zirconia beads, with 3 passes to obtain a wax dispersion.

[0466] (Preparation of Masterbatch) 1200 parts by mass of water, 500 parts by mass of carbon black (Printex35, manufactured by Dexa, DBP oil absorption=42mL / 100mg, pH=9.5), and 500 parts by mass of amorphous polyester resin 1 were mixed in a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.), and the mixture was kneaded using two rolls at 150°C for 30 minutes. Thereafter, the mixture was rolled and cooled, and pulverized with a pulperizer to obtain master batch 1.

[0467] (Preparation of oil phase) 21 parts by weight of the wax dispersion, 47 parts by weight of crystalline polyester dispersion 1, 49 parts by weight of amorphous polyester resin A, 4 parts by weight of amorphous hybrid resin 1, 17 parts by weight of master batch 1, and 30 parts by weight of ethyl acetate were placed in a container and mixed at 5,000 rpm for 60 minutes with a TK homomixer (manufactured by Tokushu Kika Co., Ltd.) to obtain an oil phase.

[0468] (Preparation of aqueous phase) 256 parts by mass of water, 12.5 parts by mass of the microparticle dispersion (W-1), 2.5 parts by mass of the microparticle dispersion (W0-1), 26 parts by mass of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7, manufactured by Sanyo Chemical Industries, Ltd.), and 24 parts by mass of ethyl acetate were mixed and stirred to obtain a milky white liquid, which was used as the aqueous phase.

[0469] (Emulsification and desolvation) In the container containing the oil phase, 14 parts by mass of prepolymer A and 0.2 parts by mass of isophorone diamine, a curing agent, were added and mixed by stirring to obtain a mixed liquid. The aqueous phase was added to the resulting mixed liquid, and the mixture was mixed with a TK homomixer at a rotation speed of 13,000 rpm for 20 minutes to obtain an emulsified slurry. Next, the emulsified slurry was placed in a container equipped with a stirrer and a thermometer, and desolvated at 30°C for 8 hours, and then aged at 45°C for 4 hours to obtain a dispersed slurry.

[0470] (Washing and drying) 100 parts by mass of the dispersed slurry was filtered under reduced pressure, and the following operations were then carried out. (1): 100 parts by mass of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered. (2): A 10% aqueous solution of sodium hydroxide was added to the filter cake of (1) until the pH reached 11, and the mixture was mixed with a TK homomixer (at 12,000 rpm for 30 minutes), followed by filtration under reduced pressure. (3): 10% hydrochloric acid was added to the filter cake of (2) until the pH reached 4 to 5, and the mixture was mixed in a TK homomixer (at 12,000 rpm for 10 minutes) and then filtered. (4): 300 parts by mass of ion-exchanged water was added to the filter cake of (3), mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered.

[0471] The operations (1) to (4) were repeated twice to obtain a filter cake.

[0472] The resulting filter cake was dried in a circulating air dryer at 45° C. for 48 hours, and sieved through a mesh having an opening of 75 μm to obtain toner base particles.

[0473] (External Addition Treatment) 100 parts by weight of the obtained toner base particles were mixed in a Henschel mixer with 0.6 parts by weight of hydrophobic silica having an average particle size of 100 nm, 1.0 parts by weight of titanium oxide having an average particle size of 20 nm, and 0.8 parts of hydrophobic silica fine powder having an average particle size of 15 nm to obtain a toner.

[0474] (Preparation of developer) A developer was prepared by mixing 5 parts by mass of the toner and 95 parts by mass of the carrier using a ball mill.

[0475] ((Creating the Carrier)) The carrier was prepared as follows. 100 parts by mass of silicone resin (organo straight silicone), 5 parts by mass of γ-(2-aminoethyl)aminopropyltrimethoxysilane, and 10 parts by mass of carbon black were added to 100 parts by mass of toluene, and dispersed for 20 minutes with a homomixer to prepare a resin layer coating liquid. Using a fluidized bed type coating device, the resin layer coating liquid was applied to the surface of 1000 parts by mass of spherical magnetite with an average particle size of 50 μm to prepare a carrier.

[0476] <Example 2> The same procedure as in Example 1 was repeated except that the amount of amorphous polyester A used in (Preparation of oil phase) was changed to 45 parts by mass, and the amount of amorphous hybrid resin 1 was changed to 8 parts by mass.

[0477] <Example 3> The same procedure as in Example 1 was repeated except that the content of Amorphous Polyester A used in (Preparation of Oil Phase) was changed to 59 parts by mass, and the content of Crystalline Polyester Dispersion 1 was changed to 37 parts by mass.

[0478] <Example 4> The same procedure as in Example 1 was repeated except that the content of the microparticle dispersion (W-1) used in (Preparation of the aqueous phase) was changed to 10 parts by mass, and the content of the microparticle dispersion (W0-1) was changed to 5 parts by mass.

[0479] <Example 5> The same procedure as in Example 1 was repeated except that the content of the microparticle dispersion (W-1) used in (Preparation of the aqueous phase) was changed to 5 parts by mass, and the content of the microparticle dispersion (W0-1) was changed to 10 parts by mass.

[0480] <Example 6> The procedure of Example 1 was repeated, except that the amount of amorphous polyester A used in (Preparation of oil phase) was changed to 67 parts by mass, the amount of amorphous hybrid resin 1 was changed to 4 parts by mass, and the amount of crystalline polyester dispersion 1 was changed to 29 parts by mass.

[0481] <Example 7> The same procedure as in Example 1 was repeated except that the content of the microparticle dispersion (W-1) used in (Preparation of the aqueous phase) was changed to 3 parts by mass, and the content of the microparticle dispersion (W0-1) was changed to 19 parts by mass.

[0482] <Example 8> The same procedure as in Example 1 was repeated except that the content of amorphous polyester A used in (Preparation of oil phase) was changed to 43 parts by mass, and the content of amorphous hybrid resin 1 was changed to 10 parts by mass.

[0483] <Example 9> The same procedure as in Example 1 was repeated except that the amorphous polyester A used in (Preparation of oil phase) in Example 1 was changed to the amorphous polyester B.

[0484] <Example 10> The same procedure as in Example 1 was repeated except that the amorphous polyester A used in (Preparation of oil phase) in Example 1 was changed to the amorphous polyester C, and the prepolymer A was changed to the prepolymer B.

[0485] <Comparative Example 1> The same procedure as in Example 1 was repeated, except that the content of the amorphous hybrid resin 1 used in (Preparation of oil phase) in Example 1 was changed to 1 part by mass.

[0486] <Comparative Example 2> The procedure of Example 1 was repeated except that the content of the microparticle dispersion (W-1) used in (preparation of the aqueous phase) was changed to 10 parts by mass, the content of the microparticle dispersion (W0-1) was changed to 5 parts by mass, and the content of the amorphous hybrid resin 1 used in (preparation of the oil phase) was changed to 1 part by mass, and the content of the crystalline polyester dispersion 1 was changed to 54 parts by mass.

[0487] <Comparative Example 3> The same procedure as in Example 1 was repeated except that the content of the crystalline polyester dispersion 1 used in (preparation of oil phase) was changed to 54 parts by mass.

[0488] <Comparative Example 4> The same procedure as in Example 1 was repeated except that the content of the microparticle dispersion (W-1) used in (Preparation of the aqueous phase) was changed to 2 parts by mass, and the content of the microparticle dispersion (W0-1) was changed to 20 parts by mass.

[0489] <Comparative Example 5> The same procedure as in Example 1 was repeated except that the amorphous hybrid resin 1 was replaced with the amorphous polyester resin A during the preparation of the oil phase.

[0490] <Proportion of the area of ​​the crystalline polyester resin in the deep region to the total area in the cross section of the toner> The obtained toners of each of the examples and comparative examples were embedded in epoxy resin and cut into slices with a thickness of 100 nm using a microtome. The cross section of the toner was then observed using a TEM to confirm the structure in which the crystalline polyester resin had come into contact with the release agent. A 0.5% aqueous solution of ruthenium tetroxide was used for dyeing. From the obtained TEM photographs, the total area of ​​the crystalline polyester resin in the toner cross section and the area of ​​the crystalline polyester resin in the deep region were measured, and the ratio of the area of ​​the crystalline polyester resin in the deep region to the total area of ​​the toner cross section was calculated. For the deep region, the radius R of the toner cross section was calculated by multiplying the major axis R of the toner cross section by the area of ​​the crystalline polyester resin in the deep region. max and minor axis R min The average value of (R max +R min ) / 2, and the area inside a perfect circle with a radius of R / 2.

[0491] <Proportion of the surface of the toner base particle occupied by crystalline polyester resin> The obtained toners of each of the examples and comparative examples were embedded in epoxy resin and cut into slices of 100 nm thickness using a microtome. The cross sections of the toners were then observed using a TEM. A 0.5% aqueous solution of ruthenium tetroxide was used for staining. From the obtained TEM images, the length of the crystalline polyester resin present on the circumference of the toner cross section and the circumference of the toner cross section were measured, and the ratio of the length of the crystalline polyester resin present on the circumference of the toner cross section to the circumference of the toner cross section, i.e., the ratio of the crystalline polyester resin occupying the surface of the toner base particle, was calculated.

[0492] <Distance between organic particles> The distance between the organic fine particles on the surface of the toner base particle constituting the toner of each of the obtained Examples and Comparative Examples was measured. First, the external additives of the toner were removed as much as possible by a release treatment using ultrasonic waves to make the toner in a state close to the toner base particle. [1] 50 ml of a 5% aqueous solution containing a surfactant (product name: Noigen ET-165, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added to a 100 ml screw tube, and 3 g of toner was added to the mixture and gently moved up and down and left and right. After that, it was stirred for 30 minutes in a ball mill so that the toner would blend into the dispersion solution. [2] Then, ultrasonic waves were applied for 60 minutes using an ultrasonic homogenizer (model VCX750, CV33, manufactured by SONICS & MATERIALS LLC) with an output of 40 W. (Ultrasonic conditions) Vibration time: 60 minutes continuous ·Amplitude: 40W ·Vibration start temperature: 23±1.5℃. ·Temperature during vibration: 23±1.5℃ [3](1) The dispersion liquid was suction filtered using filter paper (qualitative filter paper (No. 2, 110 mm), manufactured by Advantec Toyo Co., Ltd.), and then washed twice with ion-exchanged water and filtered again. After removing the liberated additives, the toner was dried. (2) The toner obtained in (1) was observed with a scanning electron microscope (SEM). First, external additives and fillers containing Si were detected by observing the backscattered electron image. (3) The image obtained in (2) was binarized using image processing software (ImageJ) to remove external additives and fillers. (4) Next, a secondary electron image was observed at the same position as in (2). Organic fine particles are not observed in the reflected electron image, but only in the secondary electron image. Therefore, the image was compared with that obtained in (3), and the fine particles present in the areas other than the remaining external additives and filler (areas other than those removed in (3)) were determined to be organic fine particles. Image processing software was used to measure the distance between the fine particles (the center-to-center distance of the fine particles). The standard deviation of the distance between the organic fine particles was calculated using formula (I), with the distance between the fine particles being x.

[0493] -Shooting conditions- Scanning electron microscope: SU-8230 Magnification: 35,000x Image capture: SE(L): Secondary electrons, BSE (backscattered electrons) Acceleration voltage: 2.0kV ·Acceleration current: 1.0μA ·Probe current:Normal Focus mode: UHR WD:8.0mm

[0494] <Toner Tg 1st , Tga of THF insoluble matter 1st , Tg of THF soluble matter 2nd , Tg of organic particles 1st > 1 g of toner was put into 100 mL of THF, and Soxhlet extraction was performed to obtain a THF soluble fraction and an insoluble fraction. This was then dried in a vacuum dryer for 24 hours to obtain a polyester resin (a mixture with crystalline polyester in Examples 9 to 11) from the THF soluble fraction, and a polyester resin was obtained from the THF insoluble fraction. These were used as the target samples. In addition, the toner Tg 1st , Toner Tg 2nd In the measurement, a toner was used as a target sample.

[0495] Next, about 5.0 mg of the target sample was placed in an aluminum sample container, the sample container was placed on a holder unit, and set in an electric furnace. Next, under a nitrogen atmosphere, the sample was heated from -80°C to 150°C at a heating rate of 1.0°C / min (first heating). After that, the sample was cooled from 150°C to -80°C at a heating rate of 1.0°C / min, and further heated to 150°C at a heating rate of 1.0°C / min (second heating). In each of the first and second heating, a DSC curve was measured using a differential scanning calorimeter ("Q-200", manufactured by TA Instruments).

[0496] From the obtained DSC curves, the analysis program in the Q-200 system was used to select the DSC curve at the first heating step, and the glass transition temperature Tg 1st Similarly, the DSC curve during the second heating was selected, and the glass transition temperature Tg 2nd asked for.

[0497] From the obtained DSC curves, the analysis program in the Q-200 system was used to select the DSC curve during the first heating, and the endothermic peak top temperature during the first heating of the target sample was determined as the melting point. Similarly, the DSC curve during the second heating was selected, and the endothermic peak top temperature during the second heating of the target sample was determined as the melting point.

[0498] In addition, unless otherwise specified, the melting points and glass transition temperatures (Tg) of the polyester resin components A, B, and C, and other components such as the release agent, are the endothermic peak top temperatures and glass transition temperatures (Tg) at the second heating. 2nd are the melting point and glass transition temperature Tg of each sample.

[0499] The toner components insoluble in THF were heated from -80°C to 150°C at a temperature rise rate of 1.0°C / min using the modulation mode with a modulation temperature amplitude of ±1.0°C / min (first temperature rise). The obtained DSC curve was then obtained by plotting "Reversing Heat Flow" on the vertical axis using the analysis program in the Q-200 system, and the onset value was taken as the glass transition temperature Tg. This resulted in Tga 1st , Tgb 1st and Tg 2nd ' was asked for.

[0500] <Evaluation of toner characteristics> Next, the toner characteristics were evaluated using each of the prepared developers as follows. The evaluation results are shown in Table 1.

[0501] [Low temperature fixability] Toner is applied on the paper at 0.8mg / cm 2 The toner was applied evenly to the paper surface using a printer (RICOH MPC 6003, manufactured by Ricoh Co., Ltd.) without a thermal fixing unit. The paper was placed on the pressure roller at a fixing speed (heat roller peripheral speed) of 213 mm / sec and a fixing pressure (pressure roller pressure) of 10 kg / cm. 2The temperature at which cold offset occurs (MFT) was measured when the sheet was passed through the above conditions. The lower the temperature at which cold offset occurs, the better the low-temperature fixing ability. (Cold offset evaluation criteria) ◎: The minimum fixing temperature is 130℃ or less ○: The minimum fixing temperature is greater than 130°C and less than or equal to 135°C. △: The minimum fixing temperature is greater than 135°C and less than 140°C ×: The minimum fixing temperature is higher than 140° C.

[0502] [Heat-resistant storage stability] After storing the toner at 50°C for 8 hours, it was sieved through a 42 mesh sieve for 2 minutes and the residual ratio on the wire mesh was measured. At this time, the better the heat-resistant storage stability of the toner, the smaller the residual ratio. The heat-resistant storage stability was evaluated based on the following evaluation criteria. (Evaluation Criteria) ◎: Residual rate is less than 5% ○: Residual rate is 5% or more and less than 15% △: Residual rate is 15% or more but less than 30% ×: Residual rate is 30% or more

[0503] [Image glossiness (gloss variation)] A copying test was conducted on POD Gloss Coat 128g / m2 (Oji Paper Co., Ltd.) using a device with a modified fixing section of the imagioMP C5002 (Ricoh Co., Ltd.). Specifically, the fixing temperature was changed from 140° C. to 160° C. in increments of 4° C., and the glossiness at each temperature was determined, and the difference between the upper and lower limits of the glossiness within the above fixing temperature range was determined. After the copying test, the image was measured for gloss at 60 degrees using a gloss meter VG-7000 (manufactured by Nippon Denshoku Industries Co., Ltd.). The fixing evaluation conditions were a paper feed linear speed of 100 mm / sec, a surface pressure of 1.0 kgf / cm 2 , and a nip width of 7 mm. ○: Less than 2 △: 2 or more, less than 4 ×:4 or more

[0504] [Cleaning ability (photoconductor contamination)] Using an image forming device (RICOH MPC 6003, manufactured by Ricoh Co., Ltd.), 50,000 sheets (A4 size landscape) of a chart with an image area ratio of 5% was outputted at 3 prints / job in a laboratory environment of 21°C and 65% RH. After that, in a laboratory environment (32°C, 54% RH), 100 sheets of a vertical band pattern (relative to the paper running direction) with a width of 43 mm and 3 charts were outputted in A4 size landscape as evaluation images, and the obtained images were visually observed to evaluate the cleaning performance based on the presence or absence of image abnormalities due to poor cleaning. (Evaluation Criteria) ⊚: Toner that has slipped through due to poor cleaning cannot be visually confirmed on the printed paper or on the photoconductor, and no streaks of toner can be confirmed even when observing the photoconductor in the longitudinal direction with a microscope. ◯: The toner that has slipped through due to poor cleaning cannot be visually confirmed on the printed paper or on the photoconductor. ×: Toner that has slipped through due to poor cleaning can be visually confirmed on the printed paper and on the photoconductor.

[0505] The ratio of the crystalline polyester resin occupying the surface of the toner base particle, the particle size of the organic fine particles, the standard deviation of the interparticle distance, and the glass transition temperature (Tg) of the toner for each example and comparative example. 1st , the glass transition temperature Tg of the toner not containing THF 1st , the glass transition temperature Tg of the THF-required portion of the toner 1st The evaluation results of the toner are shown in Table 1.

[0506] [Table 1]

[0507] From Table 1, it was confirmed that the toners of Examples 1 to 6 met the conditions for use in terms of low fixability, heat-resistant storage stability, image glossiness (gloss variation), and cleanability. In contrast, the toners obtained in Comparative Examples 1 to 4 did not meet the conditions for use in terms of at least one of low fixability, heat-resistant storage stability, image glossiness, and cleanability, and unacceptable deterioration in quality occurred. Therefore, it was confirmed that the toners obtained in Comparative Examples 1 to 4 could not simultaneously achieve all the required characteristics and had practical problems.

[0508] Thus, the toners of Examples 1 to 6 are different from the toners of Comparative Examples 1 to 4 in that the ratio of the area of ​​the crystalline polyester resin in the deep region to the total area of ​​the cross section of the toner is less than 20%, the ratio of the crystalline polyester resin occupying the surface of the toner base particle is less than 15%, and the standard deviation of the distance between adjacent organic fine particles that are not in contact with each other is 600 nm or less. As a result, the toners of Examples 1 to 6 are excellent in low fixing property, heat-resistant storage stability, image glossiness, and cleanability, and can be said to be high-quality toners.

[0509] Although the embodiment has been described above, the above embodiment is presented as an example, and the present invention is not limited to the above embodiment. The above embodiment can be implemented in various other forms, and various combinations, omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]

[0510] 1. Image forming device 311Y, 311C, 311M, 311K photoreceptor 312Y, 312C, 312M, 312K Charging device 313Y, 313C, 313M, 313K developing device (developing section) 40 Transcription section 50 Fixing unit [Prior art documents] [Patent documents]

[0511] [Patent Document 1] JP 2016-180911 A

Claims

1. A toner containing toner base particles including a crystalline polyester resin and an amorphous polyester resin, a plurality of organic fine particles arranged in a state where at least a part of the organic fine particles is embedded in the surface of the toner base particle; The organic fine particles have a volume average particle size of 10 nm to 40 nm; the content of the organic fine particles in the toner is 0.2% by mass to 5% by mass, the standard deviation of the distance between adjacent particles of the organic fine particles that are not in contact with each other is 81 nm to 590 nm; when the radius of the cross section of the toner is R, an area of ​​the crystalline polyester resin in an inner region of a perfect circle having a radius of R / 2 is 5% or more and less than 20% of a total area of ​​the crystalline polyester resin in the cross section, A toner in which the crystalline polyester resin occupies less than 15% of the surface of the toner base particle.

2. The toner described in claim 1, wherein the organic microparticles contain two types of styrene-acrylic resins.

3. The glass transition temperature Tg of the toner at the first temperature rise in differential scanning calorimetry 1st is 20°C to 50°C, The glass transition temperature Tg of the component of the toner that is insoluble in tetrahydrofuran at the first temperature rise in differential scanning calorimetry 1st 3. The toner according to claim 1, wherein the viscosity is from -40°C to 10°C.

4. A toner storage unit containing the toner according to any one of claims 1 to 3.

5. An electrostatic latent image carrier; an electrostatic latent image forming unit for forming an electrostatic latent image on the electrostatic latent image carrier; a developing section for developing the electrostatic latent image with toner to form a visible image; a transfer section for transferring the visible image onto a recording medium; a fixing unit that fixes the transferred image on the recording medium, 4. An image forming apparatus, wherein the toner is the toner according to claim 1.

Citation Information

Patent Citations

  • Toner, developer, process cartridge, image forming method, and image forming device

    JP2011197274A

  • Toner for electrostatic charge image development

    JP2015045719A

  • Toner for electrostatic charge image development

    JP2016180911A

  • Toner for electrostatic charge image development and method for manufacturing toner for electrostatic charge image development

    JP2018072655A

  • Toner for electrostatic charge image development

    JP2020067550A